Microbial network stability is linked to soil multifunctionality and functional trade-offs under long-term fertilization in a dryland agroecosystem - Fangfang Li; Xihe Wang; Yaping Huang; Xin Li; Lei Wu; Jinyu Yang; Wanli Xu; Wenju Zhang (Agriculture, Ecosystems & Environment, 2027)

Lactate-enhanced production of a cyclic β-1,2-glucan in Acetobacter pasteurianus - Yong Chen; Yihang Qi; Zhongya Zhou; Xin Liu; Yaping Sun; Ting Liu; Mengru Wu; Hui Li; Jing-yi Zhao; Zijun Xiao (Food Microbiology, 2027)

Evaluating ecological and socio-economic system dimensions to improve fisheries management in the Bohai Sea, China - Jie Yin; Jia Wo; Yunzhou Li; Ming Sun; Jacob G. Eurich; Kristin M. Kleisner; Shems B. Jud; Yi Tang; Shu Su; Yaping Ao; Yong Chen (Reviews in Fish Biology and Fisheries, 2026)

METTL3 suppresses pyroptosis in obstructive sleep apnea-associated hypertension via YTHDF2-mediated SOX4 mRNA degradation - Wenjun Zhu; Yanyan Hou; Can Yang; Yaping Tian; Linna Cao; Wenjun Li; Liang Xie; Lirong He (Journal of Physiology and Biochemistry, 2026)

Tailoring MOF/PEO interface via self-assembled deep eutectic layer for advanced solid polymer electrolyte - Jing Li; Yifan Huang; Yaping Sun; Cheng Lian; Haiping Su; Jingkun Li; Honglai Liu (Chemical Engineering Journal, 2026)

Optimizing organic resource allocation to enhance microbial necromass nitrogen accrual: Evidence from multiple long-term fertilization experiments - Jun Wang; Yaping Huang; Qiong Xiao; Dong Wu; Dongchu Li; Xin Li; Lei Wu; Yinghua Duan; Minggang Xu; Wenju Zhang (Agriculture, Ecosystems & Environment, 2026)

Augmented innate and humoral immune responses enhance early and durable rabies protection by a CD40L-overexpressing rabies vaccine - Xiao Xing; Yufang Wang; Zhimin Xiong; Die Liu; Yong Wang; Yang Hu; Yaping Liu; Yingying Li (Veterinary Microbiology, 2026)

Optimizing Holstein bovine oocyte development: Evidence-Based donor selection for OPU-IVP - Heqiang Li; Baobao Zhao; Jingya Wang; Xuexiao Song; Jieyu Wang; Yang Li; Zihan Xu; Zheng Wang; Yaochang Wei; Zhuangsheng Wang; Yaping Jin; Yongsheng Wang (Theriogenology, 2026)

Corrigendum to “Alterations in the amino acid profile of follicular fluid of cows following ovarian stimulation and its association with oocyte quality and embryonic development” [Theriogenology 2026; 118017] - Yao Li; Jie Wang; Jiajing Liang; Ning Yang; Yupeng Xu; Baoli Zhao; Mingming Liu; Xingxing Ling; Pengfei Lin; Huatao Chen; Aihua Wang; Yaping Jin; et al. (Theriogenology, 2026)

Alterations in the amino acid profile of follicular fluid of cows following ovarian stimulation and its association with oocyte quality and embryonic development - Yao Li; Jie Wang; Jiajing Liang; Ning Yang; Yupeng Xu; Baoli Zhao; Mingming Liu; Xingxing Ling; Pengfei Lin; Huatao Chen; Aihua Wang; Yaping Jin; et al. (Theriogenology, 2026)

Supplemental vitamins A, D, and E improve OPU-IVP efficiency in postpartum dairy cows by alleviating oxidative stress - Jinbang Xiao; Manyuan Tian; Zhengjie Ding; Haohao Mu; Haitao She; Heqiang Li; Bingke Wang; Hui Chen; Yonghong Jia; Yongsheng Wang; Yaping Jin; Pengfei Lin (Theriogenology, 2026)

Bilayer membrane with asymmetric wettability based on superhydrophilic/underwater superoleophobic cotton fabric for simultaneous oil-dye-water separation - Luwen Zhao; Yu Xia; Zhi Zhang; Yuan Zhu; Mingzhu Li; Jinlin Shen; Boxuan Zhu; Li Lv; Hongliang Ke; Zaisheng Cai; Yaping Zhao (Journal of Environmental Chemical Engineering, 2026)

Bamboo cellulose fiber aerogel for radioactive cobalt adsorption with ultimate volume reduction: A green and economic disposal pathway - Hongyan Chen; Zhuo Chen; Zhanquan Wang; Yu Wang; Xinyu Xie; Qin Chen; Jinchao Li; Yaping Zhang; Liang Chen (Chemical Engineering Journal, 2026)

Anomalous thermally enhanced output and ion-exchange repairability of flame-retardant waste cotton textile-based triboelectric nanogenerators - Kun Zhao; Yaping Liu; Li Chen; Mengdan Shen; Xuefeng Lu; Yuandong Li; Yong Wang; Kewei Zhang (Chemical Engineering Journal, 2026)

A bioinspired self-pumping Janus interface for wet-adhesive epidermal ECG monitoring - Zhiwei Jiang; Yaping You; Hui Zhang; Cihui Liu; Shaohong Wu; Zixiang Li; Songchao Fu; Xia Liu; Yiran Jing; Yuzhen Li; Cheng Chen; Lehao Ren (Chemical Engineering Journal, 2026)

Employment of magnetic measurements for monitoring conversion reactions in Fe3O4 anodes for lithium and sodium ion batteries - Bi Fu; Minghan Yang; Junfu Cheng; Zhanxu Chen; Yunbao Zheng; Yifang Li; Guangqi Hu; Yingji He; Chengzhi Hu; Yaping Wang (Chemical Engineering Journal, 2026)

A bone-homing DNA tetrahedral framework nucleic acids nanodevice orchestrates osteogenic regeneration to rescue postmenopausal osteoporosis - Qiumei Li; Fenglin Zhou; Shiyi Zeng; Yue Gao; Qian Shen; Yaping Wu; Chuan Ma; Yunfeng Lin; Jingang Xiao; Kui Huang (Chemical Engineering Journal, 2026)

Controlled biosynthesis of curdlan oligosaccharides with tunable degree of polymerization and their prebiotic effects on gut microbiota - Yaping Pan; Yuying Wang; Zhilei Liu; Tong Liang; Zepeng Chang; Qingyu Wang; Qijun Pan; Yun Jiang; Zhitao Li; Minjie Gao (Bioresource Technology, 2026)

GLSP ameliorates monocrotaline-induced pulmonary arterial hypertension through inhibition of the PI3K/AKT and MAPK signaling pathways - Yingying Wei; Siying Zuo; Na Deng; Haijun Guo; Liwei You; Yaping Zuo; Yan Wu; Zhangrong Chen; Wei Li; Xiaoyun Si (Journal of Molecular Histology, 2026)

Exercise-induced neuropeptidergic and neurochemical neuroadaptation in stress regulation and emotional disorders - Ziqi Wang; Zhinei Tan; Yaping Zhang; Yuzhou Li; Jinyan Lin; Yingli Xu; Yongxia Li; Ting Chen (Acta Neurologica Belgica, 2026)

Interferon-tau regulates the PGE2/PGF2α ratio via ISG15 in the goat corpus luteum during early pregnancy - Chunmei Shang; Haokun Liu; Zuhui Li; Yuanmeng Mou; Chenling Fan; Shan Liu; Yaping Jin; Pengfei Lin (Theriogenology, 2026)

Effective risks and dominant factors of drought-flood abrupt alternation events to global socio-ecological systems - Bohua Wu; Ziqi Yan; Denghua Yan; Yaping Cheng; Baisha Weng; Jianzhu Li (Journal of Hydrology, 2026)

Combined CO₂ and topographic uplift forcing on vegetation and climate change in the North China Plain since ∼6.5 Ma - Wei Liu; Likang Wang; Zhenjing Yang; Dianbao Chen; Dexuan Chen; Yaping Li; Xiaozhong Huang; Yunfa Miao; Baotian Pan (Global and Planetary Change, 2026)

Subduction-dominated processes control deep lithospheric structure and microplate tectonics of the Iranian Plateau: Insights from multi-geophysical inversions - Feiyu Zhao; Sanzhong Li; Junling Pei; Yanhui Suo; Mengxue Dai; Shengxing Zhang; Xiao Chen; Yanguo Wang; Yaping Hu; Bin Hu (Earth-Science Reviews, 2026)

Needle-like NiCo2S4 anchored on graphene-like carbon via ion-concentration regulation for hybrid supercapacitors - Jialong Li; Tong Han; C. Srinivasakannan; Shiye Cai; Gang Xue; Li Wang; Yaping Wang; Xinhui Duan (Chemical Engineering Journal, 2026)

Deep learning-enabled real-time acoustofluidic sorting for selective microalgae recovery under wastewater-relevant heterogeneous conditions - Zihan Li; Xian Jiang; Wenzhe Gong; Aoyang Tang; Yan Ma; Xia Du; Yaping Xie; Tielin Shi; Zhiyong Liu; Guanglan Liao; Lei Nie (Bioresource Technology, 2026)

GnRH supplementation in the PreOvsynch protocol targeting follicular cysts enhances synchronization and reduces days open in dairy cows - Jinbang Xiao; Manyuan Tian; Zhengjie Ding; Haohao Mu; Haitao She; Heqiang Li; Bingke Wang; Hui Chen; Yonghong Jia; Yongsheng Wang; Yaping Jin; Pengfei Lin (Animal Reproduction Science, 2026)

Prognostic factors and predictive modeling of in-hospital mortality among MDRO-positive inpatients: a retrospective cohort and GBD MICROBE study - Fan Jiang; Jian Li; Yahan Li; Yaping Yao; Ke Liu; Wei Dai; Hui Du (Antonie van Leeuwenhoek, 2026)

Grass Carp Reovirus ( GCRV ): Biology, Immune Responses and Control Strategies - Waqar Younas; Mijuan Shi; Rong Huang; Yaping Wang; Libo He; Hong Yang; Lei Zhang; Yingyin Cheng; Wanting Zhang; Lanjie Liao; Yongming Li; Bin Gui; et al. (Reviews in Aquaculture, 2026)
As the world's population grows, aquaculture is becoming a rapidly growing source of protein. Grass carp ( Ctenopharyngodon idella ) is one of the most important aquacultured species in China and has emerged as a significant commercial fish worldwide. However, grass carp reovirus (GCRV) poses a significant threat to grass carp aquaculture. This review covers GCRV biology, phylogeny, pathogenesis, immune response pathways, therapeutic approaches, and future challenges and directions. A comprehensive phylogenetic analysis describes the structure of GCRV, its entry into cells, its molecular architecture, its replication procedures and its interactions with the host, with a particular focus on the pivotal role of Pattern Recognition Receptors (PRRs). The paper explores how PRRs, such as RLRs (RIG‐I and MDA5) and TLRs (TLR3 and TLR19), are essential for identifying GCRV and initiating robust antiviral responses, particularly the interferon pathway. The paper goes on to explain the complex immune evasion tactics employed by GCRV, emphasizing how viral proteins such as VP41, VP4 and VP56 selectively target and interfere with critical components of PRR signaling cascades, such as MAVS‐TBK1 and MITA/STING, thereby reducing host immunity. Various next‐generation vaccines are being developed, including DNA, subunit, VLP and oral/mucosal platforms. These are supported by Chinese herbal and chemical antivirals. According to CRISPR/Cas9, experimental RNAi, PI4KB and SOCS3a/3b are host genes that can be altered to increase grass carp resistance to GCRV. This research offers significant insights into viral cell invasion and strengthens innate and adaptive immunity, enabling safer, more practical and multilayered control in aquaculture.

Bioequivalence evaluation of risedronate sodium in healthy Chinese participants under fasting conditions: a randomized, open-label, single-dose, three-period, partial replicate crossover study - Ling He; Dan Hong; Weiyong Li; Yaping Hu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Acupoint hot compress for labor-pain management: a randomized, parallel-group, controlled trial - Fangfang Wang; Leyi Fu; Xinyue Li; Yuqun Pu; Lianqing Gong; Lin Zhou; Lanxiang Fu; Yaping Chen; Mali Chen; Yue Qin; Xiaoying Lyu; Ye Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

In situ generation of NKG2D CAR T/NK cells via a tumor-targeted lipoplex for enhancing cancer immunotherapy - Xiaoxuan Xu; Wenzhe Yi; Xiangshi Sun; Zhiwen Zhao; Jialin Duan; Ting Wu; Xiaoting Shan; Jie Li; Dangge Wang; Yaping Li (Science Bulletin, 2026)

Retrieval of a desert steppe degradation index from hyperspectral data using self-supervised spectral representation learning - Liang Wang; Wenxia Zhang; Haichao Wang; Yufei Gao; Yuqi Liu; Qian Wang; Yaping Wang; Jianjun Li (Remote Sensing Applications: Society and Environment, 2026)

Wettability-switchable deep bed filtration for efficient oily wastewater treatment - Song Xichen; Yan Yaping; Zhang Tingting; Zhou Jianqiang; Wang Xiaojuan; Wang Zhezhe; Lin Jialong; Wang Ting; Song Xiaosan; Dai Liang; Wang Gang; Gao Suxia; et al. (Journal of Hazardous Materials, 2026)

Loss of foxp3a drives sex-specific immune-metabolic remodeling across the gut-liver-gonad axis in zebrafish - Yuhang Hu; Deinyefa Godfree Igbiriki; Nan Wu; Jialin Li; Junheng Liu; Jiuwu Yin; Jinping Duan; Xianmei Li; Zhixian Qiao; Feng Xiong; Yingyin Cheng; Wanting Zhang; et al. (Fish & Shellfish Immunology, 2026)

Promoting high energy density Mn-based layered oxide cathodes via surface structural regulation for sodium-ion batteries - Maohan Liu; Lingyi Kong; Xinyu Zhang; Yaping Yan; Haiyan Hu; Hanshen Xin; Jiayang Li; Yubin Niu; Yanfang Zhu; Yao Xiao (Chemical Engineering Journal, 2026)

Grass carp reovirus utilizes multiple endocytic pathways for host cell entry - Xiaowen Zou; Yongming Li; Zuoyan Zhu; Yaping Wang; Libo He (Aquaculture, 2026)

Neural activation patterns underlying football decision-making: evidence for the neural proficiency hypothesis - Ju Li; Yaping Cao; ZhongCheng Li; Xudong Zhao; Zhe Qin; Minghao Huang; Jian Lang; Xiaopeng Chi (Brain Imaging and Behavior, 2026)

Exploring contributions and responses of microbial quantity and diversity to coastal seasonal hypoxia - Guihao Li; Jiarong Hu; Pengfei Zheng; Ping Zhu; Yaping Wang; Songbao Zou; Xiaoli Zhang; Eleni Gentekaki; Song Sun; Aolin Zhu; Jun Gong (Marine Pollution Bulletin, 2026)

Nitrogen limitation enhances Irgarol 1051 toxicity by aggravating PSII photoinhibition in the marine diatom Thalassiosira weissflogii - Yuheng An; Shumin Zeng; Futian Li; Jun Wang; Xuexia Zhu; Juntian Xu; Yaping Wu (Marine Environmental Research, 2026)

Bisphenol A exposure disrupts the circadian clock system and impairs glycolipid metabolic function in mice liver - Hao Dong; Wenli Ding; Bonan Xiao; Cuimei Li; Haizhen Jiang; Wanghao Yang; Dan Li; Chao Li; Haisen Zhang; Dengke Gao; Aihua Wang; Yaping Jin; et al. (Food and Chemical Toxicology, 2026)

Fluid–structure interaction training of integral conservation physics-informed neural networks for blood flow in elastic vessels - Youqiong Liu; Li Cai; Yaping Chen; Qingsheng Liu (Computer Physics Communications, 2026)

High porosity poly(porous liquid)s based on multiple hydrogen bonds for rapid ammonia response - Yisong Liu; Jing Zhang; Shizhang Li; Fangfang Su; Yangyang Xin; Yating Zhang; Jinliang Xie; Dongdong Yao; Yaping Zheng (Chemical Engineering Journal, 2026)

Performance optimization and application advances of cellulose-based triboelectric materials for high-humidity environments - Yakun Mou; Yuhang Qiu; Mingyang Li; Yaping Zeng; Yanniu Xu; Dengjun Lu (Carbohydrate Polymers, 2026)

Synergistic enhancement of sodium storage in bamboo-derived hard carbon via Ni nanoparticle incorporation and P-doping - Wanquan Liu; Liu Wang; Wenjing Lu; Yong Cheng; Yu Chen; Enze Ren; Zhenyao Wang; Jing Wu; Xinhui Li; Yaping Zeng (Biomass and Bioenergy, 2026)

Coupling near infrared spectroscopy with machine learning algorithms for simultaneously detecting multiple microplastics in soil - Jia Long; Xi Li; Renjie Yang; Guimei Dong; Yaping Yu; Huiyong Shan (Journal of Soils and Sediments, 2026)

Deformation and Reconstruction of Coastal Typhoon Wind Fields in Hangzhou Bay - Li Li; Jiayi Guo; Zhiguo He; Tao Feng; Yuezhang Xia; Honghua Zou; Yaping Zha; Rong Zhou; Ye Zhu; Wenjun Zhu (Journal of Marine Science and Engineering, 2026)
Coastal typhoon deformation plays a critical role in determining typhoon tracks, intensity changes, precipitation and related flooding, storm surges, and typhoon waves, and thus is highly associated with coastal disaster patterns. This study proposes a three-level framework for typhoon wind field modeling through the integration of geometric characterization with physical-informed reconstruction. At its core, an elliptical fitting method is developed based on second-order moments to quantify the structural asymmetries. This geometric fitting method is incorporated into the reconstruction method of Holland–Miyazaki, creating a physically consistent model capable of simulating typhoon deformation processes during landfall. Validation through high-resolution Weather Research and Forecasting (WRF) simulations of Typhoon Chan-hom (2015) demonstrates the framework’s effectiveness, capturing elliptical eyewall deformation with aspect ratios exceeding 1.5, primarily driven by coastal topography and surface friction interactions. The method is further validated through Typhoon Mitag (2019), with mean wind component errors below 1 m/s, the average correlation coefficients surpassing 0.9, and wind direction mean absolute errors largely below 10°. This research provides a practical framework for quantifying and characterizing the wind field deformation during typhoon landfall in coastal regions, thereby supporting ther operational forecasting and disaster reduction in vulnerable coastal regions.

Large-scale farming enhances soil health in contrast to smallholder management: Insights from a field survey - Xin LI; Dong WU; Yaping HUANG; Xiao YANG; Gilles COLINET; Caroline DE CLERCK; Wenju ZHANG; Minggang XU; Jeroen MEERSMANS (Pedosphere, 2026)

Seawater acidification accelerates growth but hastens decline in batch cultures of the marine diatom Thalassiosira pseudonana - Haiyang Zong; Zihao Sun; Dongmei Lv; Yu Shang; Yaping Wu; Juntian Xu; Futian Li (Marine Environmental Research, 2026)

Tuning CO2 separation of Type I UiO-66 porous liquids by varying the size of porous hosts - Shuangshuang Long; Jingwen Wang; Shuqian Meng; Yaxin Liu; Jing Zhang; Zihao Ren; Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Libing Qian; Wenwu Zhou; et al. (Journal of Environmental Chemical Engineering, 2026)

Transcriptome and eQTL analysis reveal the novel molecular mechanism underlying salt tolerance in the phytochrome B mutant - Conghui Jiang; Yanan He; Lixia Xie; Wen Li; Yaping Li; Yongbin Peng; Jinjun Zhou; Guanhua Zhou; Shasha Wang; Chongke Zheng; Xianzhi Xie (Plant Cell Reports, 2026)

BAMBI modulates proliferation, apoptosis, and hormone secretion in Jinding duck granulosa cells - Li Li; Xiaopan Liu; Changtao Liu; Chengfu Pan; Linli Zhang; Qingwu Xin; Zhongwei Miao; Liang Huang; Yuwei Li; Yaping Zhang; Qinlou Huang; Nenzhu Zheng; et al. (Animal Reproduction Science, 2026)

Chemically converted volume-resilience interface enables high-capacity zinc anode - Mingzhu Li; Xinyue Dou; Zhexuan Liu; Yaping Wang; Shuquan Liang; Guozhao Fang (Science Bulletin, 2026)

Linear time-lag effects and nonlinear interactions of global drought-flood abrupt alternation in responses to multiple factors - Bohua Wu; Ziqi Yan; Denghua Yan; Yaping Cheng; Jianzhu Li (Journal of Hydrology, 2026)

Blueberry juice fermented by a high β-glucosidase-producing lactic acid bacterium mitigates skin aging by modulating gut microbiota - Shasha Cheng; Yaqi Liang; Yaping Zheng; Hongxuan Li; Yu Zhang; Yujun Jiang (Food Bioscience, 2026)

A Serpine1-F2-PAR1 axis facilitates apoptosis and disease severity during GCRV infection in grass carp - Yangyang Li; Liangming Chen; Bin Gui; Changchun Yu; Jinyan Lei; Yuxuan Shao; Haiping Liu; Zuoyan Zhu; Yaping Wang; Rong Huang (Fish & Shellfish Immunology, 2026)

Coordinative interlocking stabilizes MOFs for enhanced structural and antibacterial performance - Jiayuan Wang; Yaping Zhang; Tingyao Li; Kai Wang; Rongmin Wang; Yufeng He; Pengfei Song (Chemical Engineering Journal, 2026)

Trio-active bone scaffold with multivalent ion doping establishes an osteo–angio–immune bone regenerative axis - Jiren Yan; Xiang Li; Teng Ye; Weinan Cheng; Yaping Li; Gen Wen; Fei Zhang; Linyang Chu (Chemical Engineering Journal, 2026)

Early nut exploitation and its potential for the adaptation of hunter-gatherers to climate change during the LGM in southern China - Qingjiang Yang; Keliang Zhao; Lingxia Zhao; Xinying Zhou; Lili Lu; Yaping Zhang; Lizhao Zhang; Jian Wang; Xinyi Lu; Xiaoqiang Li (Science China Earth Sciences, 2026)

Grass carp TMEM33 promotes GCRV replication by targeting MAVS for degradation and suppressing host antiviral immune response - Qian Wang; Zichao Peng; Rong Deng; Yongming Li; Zuoyan Zhu; Yaping Wang; Libo He; Jing Lu (Marine Life Science & Technology, 2026)

Characterisation of ginsenosides composition in processed American ginseng products using UPLC-MS coupled with chemometric analysis - Chang Wang; Xiaolei Tang; Haiyu Chen; Yaping Wang; Xitong Yuan; Daqing Zhao; Baotai Huang; Li Liu; Bin Qi (Natural Product Research, 2026)

Corrigendum to “Busulfan plus cyclophosphamide induced spermatogenic dysfunction and recovery: A dynamic change perspective” [Toxicol. Lett. 417(2026) 111833] - Tianyu Li; Zhichen Tang; Yaping Song; Min Su; Xiao Liu; Fuping Li; Xing Wei; Xiaolei Luo; Bin Zhou; Yanyun Wang; Lin Zhang (Toxicology Letters, 2026)

Dynamic hydrogen buffer integrated with single Pt sites for enhanced durability of high-temperature proton exchange membrane fuel cells - Yabin Xu; Jing Tian; Li Wang; Jiuli Xia; Yandong Wu; Qie Liu; Jingjing Wang; Shiqian Du; Tingting Han; Miaoyu Li; Zuyao Jiang; Yaping Gu; et al. (Science Bulletin, 2026)

Removal performance and mechanisms of microplastics by superhydrophobic medium - Zhang Tingting; Cheng Wenqing; Wang Xiaojuan; Yan Yaping; Song Xichen; Zhou Jianqiang; Liu Xiuyun; Gao Suxia; Li Hao; Liu Jianlin; Cao Lianbao; Li Wei; et al. (Journal of Environmental Chemical Engineering, 2026)

Tetracycline-derived N/P co-doped porous graphene-like carbon for effective removal of tetracycline: Synergistic adsorption-degradation mechanism - Shiye Cai; Chuanze Ma; C. Srinivasakannan; Gang Xue; Li Wang; Yaping Wang; Xinhui Duan (Journal of Environmental Chemical Engineering, 2026)

UiO-66 porous liquids with synergistic catalytic effects for promoting efficient CO2 conversion - Yaru Lu; Ruyu Bai; Dechao Wang; Yangyang Xin; Weirui Zhang; Fangfang Su; Zheng Dong; Wendi Fan; Yating Zhang; Fangli Yu; Xin Li; Yingying Zhou; et al. (Chemical Engineering Journal, 2026)

Genomic insights into recurrent demographic collapses and recovery dynamics in Tibetan antelopes (Pantholops hodgsoni) - Weimin Kuang; Hongfeng Zhang; Yingli Jiang; Han Hu; Wei Huang; Yaping Zhang; Xiaomin Wu; Li Yu (Science China Life Sciences, 2026)

Targeting the gut-liver axis with dietary polyphenols to ameliorate metabolic dysfunction-associated steatotic liver disease: advances in molecular mechanisms - Zuomin Hu; Zeyu He; Yuyan Wang; Zhongxing Chu; Yaping Zhou; Wen Li; Jun Lu; Qinlu Lin; Feijun Luo (Critical Reviews in Food Science and Nutrition, 2026)

Busulfan plus cyclophosphamide induced spermatogenic dysfunction and recovery: A dynamic change perspective - Tianyu Li; Zhichen Tang; Yaping Song; Min Su; Xiao Liu; Fuping Li; Xing Wei; Xiaolei Luo; Bin Zhou; Yanyun Wang; Lin Zhang (Toxicology Letters, 2026)

Long-term fertilization-induced increases in glomalin-related soil protein depend on phosphorus input and aggregate stability across climatic zones - Hongbo Yang; Guanmo Li; Dong Wu; Qiong Xiao; Xin Li; Yaping Huang; Jeroen Meersmans; Gilles Colinet; Minggang Xu; Wenju Zhang (Soil and Tillage Research, 2026)

Selective CO2 photoreduction to acetate enabled by charge-enriched interface sites confined in metal nanoclusters - Juncheng Zhu; Yang Wu; Jun Hu; Zijia Lin; Zexun Hu; Mingyu Wu; Runhua Chen; Kai Zheng; Wenxiu Liu; Bangwang Li; Junfa Zhu; Yang Pan; et al. (Science Bulletin, 2026)

Synchrony of prehistoric agricultural evolution and drought events in the North China Plain - Yanpeng Li; Shengrui Li; Hai Xu; Keliang Zhao; Guanhan Chen; Yaping Zhang; Jiacheng Ma; Junchi Liu; Yong Ge; Yan Zheng; Xinying Zhou; Xiaoqiang Li (Quaternary Science Reviews, 2026)

Urban land surface temperature prediction by integrating LSTM and geospatial information: A case study of Kunming, China - Ronghui Li; Yaping Zhang; Xu Chen (Journal of Cleaner Production, 2026)

Characterization of Neomegalonema-dominated granulation in aerobic granules bioreactor: Evidence for stable filamentous granulation and quorum sensing-related activities - Lili Sun; Hanquan Wen; Lu Ding; Chao Qin; Mingxi Chen; Shike She; Xinchao Zhu; Jian Wang; Zengyang He; Yaping Zhang; Zhiqiang Xu; Quan Shu; et al. (Environmental Research, 2026)

Multi-objective Optimization of Sponge City Storage Tank Considering Inlet and Outlet Water Conditions-based on NSGA-II Algorithm - Wang Xiaojuan; Ma Yingqiang; Li Hao; Qin Jie; Xiao Yifei; Yan Yaping; Zhang Tingting; Gao Suxia; Li Jiapeng; Liu Jianlin; Cao Lianbao; Li Wei; et al. (Water Resources Management, 2026)

Temperature-constrained sorption of inorganic and organic selenium by Fe-oxide minerals: Significance for selenium bioavailability in Earth's critical zone - Kunfu Pi; Qianyong Liang; Yiqun Gan; Yaping Zhang; Tao Gu; Li Zhang (Applied Geochemistry, 2026)

Based on sensory evaluation, E-nose, and GC-IMS analysis of volatile component differences in various kinds of sheep fats - Yaping Wang; Xiaolei Tang; Xitong Yuan; Hanying Xu; Yuxi Liu; Yaling Yang; Zhihui Lin; Siming Wang; Bin Qi; Li Liu (Natural Product Research, 2026)

A quantitative method of feeding demand for M. salmoides based on multi-source information fusion - Yaping Li; Hequn Tan; Yiren Zhang; Xuefei Liu (Biosystems Engineering, 2026)

An mRNA microsphere vaccine inhibiting overactivation of DNA sensing mechanisms - Fangke Zhang; Jiancheng Zheng; Fei Wang; Yaping Zhuang; Yunkai Tang; Juan Wang; Yawei Du; Wei-Li Zhao; Min Lu; Weiguo Hu; Wenguo Cui (Science Bulletin, 2026)

Study on the removal and ecological risk of microplastics in road runoff by collapsible loess bioretention facilities - Wang Xiaojuan; Yan Yaping; Song Xichen; Zhou Jianqiang; Liu Xiuyun; Zhang Tingting; Gao Suxia; Li Jiapeng; Liu Jianlin; Cao Lianbao; Li Wei; Wei Bigui (Process Safety and Environmental Protection, 2026)

Heuristic resistance-driven graph approach for preferential flow pathway identification in 3D discrete fracture networks - Lei Ma; Jixian Li; Yaping Deng; Di Han; Haichun Ma; Xuelin Cui; Jiazhong Qian (Journal of Hydrology, 2026)

Spatiotemporal dynamics of microplastics in urban stormwater runoff: Functional area effects and transport pathways (Shanghai, China) - Junhao Li; Bowen Yu; Chengjin Cao; Liuxing Wu; Yaping Zhao; Ruiyun Zhu; Yangyang Hu; Minsheng Huang; Lei Wang; Xinlin Yan (Journal of Contaminant Hydrology, 2026)

Crosslinked polymer aerogel with multiple binding sites for efficient uranium separation from uranium-containing wastewater - Yaping Jian; Jiacheng Zhang; Xuewen Cao; Jipeng Li; Qin Peng; Xuefeng Tian; Jianfei Du; Yihui Yuan; Ning Wang (Environmental Research, 2026)

Hydrogen bonding network induced by ambipolar small molecules facilitates high-performance all-solid-state Li batteries - Jing Li; Ruiqi Chai; Yaping Sun; Hengyi Wang; Cheng Lian; Haiping Su; Jingkun Li; Honglai Liu (Chemical Engineering Journal, 2026)

Confined antisolvent precipitation enables efficient drug encapsulation in microgels for effective gouty arthritis therapy - Lumin Yang; Jinhui Lin; Shuxian Wang; Zhenyang Wei; Xiaolong Zhan; Mingyu Zhu; Yaping Ding; Wei Li (Chemical Engineering Journal, 2026)

Hierarchical PBO/Mica/MOF-303 composite films for tri-functional triboelectric nanogenerators: Enhanced charge density, flame retardancy, and humidity resistance - Yaping Liu; Mengdan Shen; Yuan Ye; Chaohui Zhang; Li Chen; Kun Zhao (Chemical Engineering Journal, 2026)

Emerging graphitic carbon nitride-based piezocatalysts for multifunctional applications: Environmental remediation, renewable energy and antibacterial technology - Yaping Gan; Shuqi Li; Khan Khalid; Gebrehiwot Gebreslassie; Mengru Li; Abera Beyene Gebresilassie; Xuezhi Liu; Lianjun He; Bin Lin (Chemical Engineering Journal, 2026)

Effects of thermal alkaline hydrolysis and biochar addition on anaerobic digestion of sewage sludge and fate of antibiotic resistance genes - Ruoxin Li; Chunsheng Qiu; Xu Chen; Nannan Liu; Yaping Zhang; Li Qi; Shaopo Wang (Bioresource Technology, 2026)

Influences of microplastic-dissolved organic matter-arsenic interactions on arsenic fate in geogenic contaminated groundwater: Mechanistic insights from kinetic-thermodynamic investigations and modeling - Yaping Zhang; Kunfu Pi; Xianjun Xie; Ziyi Xiao; Jianbo Shi; Qianyong Liang; Yuxia Li (Applied Geochemistry, 2026)

Quantitative and qualitative comparison of grain-size parameters in different types of sediments using graphic and moment methods - Yuehua Qi; Mingliang Li; Gaocong Li; Jieping Tang; Lintao Zhao; Yaping Wang; Mingming Yuan (Acta Oceanologica Sinica, 2026)

Resveratrol can inhibit porcine reproductive and respiratory syndrome virus infection in vitro and in vivo by inhibiting PI3K/Akt signaling pathway - Yaping Chen; Wenshuang Chen; Xinqi Song; Xinyi Zhao; Li Yang; Ruoyu Zhao; Meilong Song; Bingbing Zhang; Dongbo Sun (Veterinary Microbiology, 2026)

Field-free topological spin textures enable spin selectivity for spin light-emitting diodes - Yongping Wei; Shuo Cao; Chenhao Zhang; Xinran Wang; Sihao Ren; Hongshu Li; Yi Yang; Jiangpeng Zhou; Mingyu Chen; Shiming Wu; Weisheng Zhao; Xichao Zhang; et al. (Science Bulletin, 2026)

Triazine herbicides inhibit phytoplankton photosynthesis in the East China Sea: A species-specific assessment - Yaping Wu; Xiangyu Li; Peijian Ding; Huifang Li; Juntian Xu (Marine Environmental Research, 2026)

The effects of increased evapotranspiration on precipitation in the Yellow River Basin - Haoyu Zhang; Shuai Wang; Changjia Li; Zidong Li; Yaping Wang; Qinhan Ye (Journal of Hydrology, 2026)

Carbonic anhydrase modulates photosynthetic responses to UV radiation in diatoms across temperature gradients - Xiangyu Li; Yuheng An; Juntian Xu; Yaping Wu; John Beardall (Journal of Photochemistry and Photobiology B: Biology, 2026)

Three-dimensional discrete fracture network identification based on deep learning and reversible jump Markov chain Monte Carlo algorithm - Zhenting Sun; Lei Ma; Quan Li; Yaping Deng; Han Qiu; Haichun Ma; Cihai Chen; Yongshuai Yan; Jiazhong Qian (International Journal of Rock Mechanics and Mining Sciences, 2026)

Grass carp (Ctenopharyngodon idella) Kat5 mediates P53 acetylation to induce apoptosis and promotes GCRV replication - Bao Liu; Chuxin Wu; Xianggao Meng; Tingting Yu; Xucheng Zhang; Jing Liu; Mingzhi Li; Yaping Weng; Huiling Mao; Chengyu Hu; Lingbao Kong; Meifeng Li (Fish & Shellfish Immunology, 2026)

Effects of roads on animals and mitigation measures in Asia - Haotong Su; Yun Wang; Qilin Li; Yangang Yang; Abudusaimaiti Maierdiyali; Shuangcheng Tao; Yaping Kong; Jiding Chen; Jiapeng Qu; Yongshun Han; Aili Kang; Shu Chen; et al. (Biological Conservation, 2026)

Effect of thermal alkaline and thermal hydrolysis on the methane production and antibiotic resistance genes removal during sewage sludge anaerobic digestion - Ruoxin Li; Chunsheng Qiu; Nannan Liu; Wen Zhang; Xu Chen; Yaping Zhang; Chenchen Wang; Shaopo Wang (Biocatalysis and Agricultural Biotechnology, 2026)

Simultaneously promoting gellan lyase expression and gellan oligosaccharide production by gellan gum co-feeding during Pichia pastoris fermentation - Tong Liang; Yuying Wang; Feiyang Duan; Yaping Pan; Zepeng Chang; Qijun Pan; Yun Jiang; Zhitao Li; Minjie Gao (Systems Microbiology and Biomanufacturing, 2026)

High-throughput screening of per- and polyfluoroalkyl substances in human plasma using biocompatible solid-phase microextraction coupled with mass spectrometry via microfluidic open interface - Yaping Li; Emir Nazdrajić; Wei Zhou; Janusz Pawliszyn (Analytica Chimica Acta, 2026)

An Advanced Fluorescent Molecularly Imprinted Sensor Based on Carbon Quantum Dots for Highly Sensitive Detection of 6-Mercaptopurine - Yinuo Liu; Zhengyuan Dai; Ying Wang; Shanshan Fu; Li Li; Yaping Ding (Journal of Fluorescence, 2025)

Multi-modal feature integration from UAV-RGB imagery for high-precision cotton phenotyping: A paradigm shift toward cost-effective agricultural remote sensing - Xiaoyu Zhi; Qiaomin Chen; Yingchun Han; Beifang Yang; Yaru Wang; Fengqi Wu; Shiwu Xiong; Yahui Jiao; Yunzhen Ma; Shilong Shang; Tao Lin; Yaping Lei; et al. (Computers and Electronics in Agriculture, 2025)

Future climate change exacerbates streamflow depletion in the Wei River Basin, China - Hongli Chen; Lijing Fan; Qiang Li; Yaping Wang; Dengfeng Liu; Fubo Zhao (Journal of Hydrology, 2025)

BFlow and Eckhardt methods perform best among non-tracer-based baseflow separation methods - Qiaoqiao Wang; Qiang Li; Yanli Qin; Xuanjiao Chai; Hongli Chen; Yaping Wang; Mingfang Zhang; Dengfeng Liu (Journal of Hydrology, 2025)

Deep insights into LDH reconstruction for enhanced capacitive deionization - Xiaohong Shang; Jinguo Hu; Yaping Yan; Siyu Li; Jiameng Diao; Haoyu Wang; Bin Hu; Hao Wang (Journal of Environmental Chemical Engineering, 2025)

Effects of CeO2 sulfation and surface modification on NH3-SCR catalytic performance and SO2 resistance of VW/Ti catalysts - Boya Zhang; Jian Gao; Jiawei Li; Kai Shen; Yaping Zhang (Journal of Environmental Chemical Engineering, 2025)

Metabolic engineering of blueberry juice by Lactiplantibacillus plantarum JM065: Fermentation optimization - Shasha Cheng; Yaping Zheng; Hongxuan Li; Yujun Jiang; Yu Zhang (Food Chemistry, 2025)

Highly sensitive and wide-range quantification of bovine αS1-casein in foods for predicting potential milk allergenicity using an IgE multi-epitope-specific antibody - Caiyi Shen; Liming Li; Caiyun Long; Yunbiao Luo; Yaping Dong; Jinyu Yu; Yi Yao; Guanrong Hu; Xin Li; Hongbing Chen; Shengfa He (Food Chemistry, 2025)

Lanthanide-based MOFs with metal-node-modulated energy transfer for multifunctional X-ray imaging platforms - Chenrui Wang; Haitao Li; Jiankun Xue; Yaping Chen; Lian Wang; Xieming Xu; Shuaihua Wang; Rong Li (Chemical Engineering Journal, 2025)

Anti-inflammatory Effects of Membrane Vesicles from Eubacterium rectale via the NLRP3 Signal Pathway - Hongxia Zhang; Yanan Zhao; Dengfu Li; Haixia Li; Zhu Wang; Lu Zhang; Huafeng Niu; Yuchen Huang; Chenchong Zhao; Yaping Jin; Dong Zhou (Probiotics and Antimicrobial Proteins, 2025)

Retraction Note: Carnosic acid nanocluster-based framework combined with PD-1 inhibitors impeded tumorigenesis and enhanced immunotherapy in hepatocellular carcinoma - Wenhua Wu; Yaping Li; Xiaokang Wu; Junrong Liang; Weiming You; Xinyuan He; Qinhui Feng; Ting Li; Xiaoli Jia (Functional & Integrative Genomics, 2025)

Soil and enzymatic C:N:P stoichiometry response to carbon and nutrient input: evidence from long-term fertilization experiments - Qiong Xiao; Yaping Huang; Guoping Chen; Kailou Liu; Yu Jiang; Boku Zhou; Ping Zhu; Xiaori Han; Junyong Ma; Shutang Liu; Shaomin Huang; Aijun Zhang; et al. (Plant and Soil, 2025)

MXene-decorated carbonized MOF nanofluids with hybrid ionic liquids for enhanced solar-thermal conversion - Fangfang Su; Jiahe Liang; Zhongjie He; Yangyang Xin; Yisong Liu; Weirui Zhang; Zhuojun Mao; Lijun Yuan; Yaping Zheng; Xiaoqian Li (Chemical Engineering Journal, 2025)

Enhancing the identification of malonylation sites using AlphaFold2 and ensemble learning - Linlin Xu; Yuting Qian; Jiayi Yang; Xiaowei Xu; Zhiqiang Li; Yanhan Wang; Enhui Lv; Xingxing Kang; Hongwei Zhang; Yaping Lu; Fei Wang; Xin Liu (Molecular Diversity, 2025)

Transcription factor OxyR regulates peroxidase levels to enhance Brucella's defense against oxidative stress - Yunyi Zhai; Hui Wang; Guangdong Zhang; Bin Li; Ziyang Diao; Lei Chen; Lulu Tian; Feijie Zhi; Junmei Li; Dong Zhou; Wei Liu; Yaping Jin; et al. (Veterinary Microbiology, 2025)

Corrigendum to “The role of ribosomal protein StRPS5 in mediating resistance of Solanum tuberosum plants to Phytophthora infestans” [Plant Sci. 357 (2025), 112539] - Jing Liu; Yaping Hu; Xiaoqing Lu; Jifen Xu; Hongyang Wang; Wei Tang; Canhui Li (Plant Science, 2025)

Corrigendum to “The role of ribosomal protein StRPS5 in mediating resistance of Solanum tuberosum plants to Phytophthora infestans“ [Plant Sci. 357 (2025) 112539] - Jing Liu; Yaping Hu; Xiaoqing Lu; Jifen Xu; Hongyang Wang; Wei Tang; Canhui Li (Plant Science, 2025)

Testing and applying analytical depletion functions for multiple pumping wells in two hydrogeological landscapes - Lijing Fan; Hongli Chen; Qiang Li; Kunpeng Li; Yaping Wang (Journal of Hydrology, 2025)

Environmental variables affect the effectiveness of ecosystem services of ecological restoration project: Evidence from Xiangjiang River Basin-Dongting Lake - Shu Fu; Jianjun Zhang; Yufei Li; Wei Chen; Yaping Zhang; Kexin Yi; Yixin Dai (Journal of Cleaner Production, 2025)

Bioreduction-assisted synthesis of Co nanoclusters for selective singlet oxygen generation in ciprofloxacin degradation - Yuning Fan; Wenqian Zhang; Yaping Geng; Jiangjun Lin; Yefei Su; Kai Teng; Jiajie wu; Qing Qu; Lei Li (Journal of Environmental Chemical Engineering, 2025)

Environmental tobacco smoke exposure in pregnant women and thyroid hormone levels in newborn cord blood: A birth cohort in China - Tengwei Gui; Yan Li; Yaping Liu; Jirong Li; Tong Luo; Shuqi Chen; Xiaoxiao Song; Xia Xiao (Environmental Pollution, 2025)

Alamandine inhibits pathological retinal neovascularization by targeting the MrgD-mediated HIF-1α/VEGF pathway - Kun Zhao; Yaping Jiang; Wen Huang; Yukang Mao; Yihui Chen; Peng Li; Chuanxi Yang (Journal of Zhejiang University-SCIENCE B, 2025)

Impact of wind and wave on the expansion of the Changjiang River plume in winter - Gaolei Cheng; Yaping Wang; Shaotian Li; Shiqiu Peng; Yuhang Zhu (Acta Oceanologica Sinica, 2025)

Assessment for the wildlife crossing structures along the Qinghai-Tibet railway - Abudusaimaiti Maierdiyali; Yun Wang; Jiding Chen; Runsheng Li; Mei Luo; Xueyang Li; Yangang Yang; Shuangcheng Tao; Yaping Kong; Hao Wang; Zhi Lu (Transportation Research Part D: Transport and Environment, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Fabric-based composite membrane for simultaneous emulsion separation and self-powered real-time monitoring - Chengcheng Li; Chengjian Yao; Keru Hou; Jie Wang; Peibo Du; Jinping Zhang; Yinjie Chen; Xing Su; Yaping Zhao; Zaisheng Cai (Journal of Hazardous Materials, 2025)

Research progress on properties and applications of triboelectric nanogenerators based on cellulosic triboelectric aerogels - Yuhang Qiu; Yakun Mou; Xunxiao Wu; Yaping Zeng; Yanniu Xu; Mingyang Li; Dengjun Lu (Chemical Engineering Journal, 2025)

Unraveling the chrono-regulatory function of PhoP in nitrogen metabolism: A multi-scale engineering framework aimed at optimizing the synthesis of poly-γ-glutamic acid in Bacillus licheniformis - Qing Zhang; Shisi He; Zhihao Zhu; Fangzhou Cheng; Yaping Jin; Wanying Zhu; Fan Yang; Yaozhong Chen; Mengyuan Zhang; Xin Li; Dongbo Cai; Shouwen Chen (Chemical Engineering Journal, 2025)

Mutation in maize chloroplastic polypeptide chain release factor (ZmcpRF1) affects chloroplast development and leaf color - Hao Chen; Haixiao Dong; Xiaohui Shan; Yuan Jiang; Shipeng Li; Hongkui Liu; Shengzhong Su; Yaping Yuan (Planta, 2025)

Global Non-site Regional Visibility Seasonal Forecast Integrating Geographical Distance - Shuaiwen Wu; Siyu Chen; Yaping Shao; Yue Zhang; Wenhan Li; Shasha Qiao (Aerosol Science and Engineering, 2025)

The role of ribosomal protein StRPS5 in mediating resistance of Solanum tuberosum plants to Phytophthora infestans - Jing Liu; Yaping Hu; Xiaoqing Lu; Jifen Xu; Hongyang Wang; Wei Tang; Canhui Li (Plant Science, 2025)

Integrated coordination of production scheduling, preventive maintenance, and energy conservation in flexible manufacturing environments - Yu Wang; Tangbin Xia; Yaping Li; Shuo Gao; Dong Wang; Lifeng Xi (Journal of Cleaner Production, 2025)

The interspecies relationships among the wildlife crossing structures of the Qinghai-Tibet Railway - Abudusaimaiti Maierdiyali; Yun Wang; Jiding Chen; Runsheng Li; Yangang Yang; Shuangcheng Tao; Yaping Kong; Zhi Lu (Journal for Nature Conservation, 2025)

Screening of siderophore-producing bacteria isolated from marine environments - Xiang Zeng; Guangyu Li; Yaping Du; Tong Yu; Qiliang Lai; Liping Wang; Zongze Shao (Acta Oceanologica Sinica, 2025)

Intensive oyster farming alters the microbial-regulated blue carbon storage in sediment - Xin Sun; Yihua Sun; Peilong Li; Yaping Gao; Ming Han; Peidong Zhang (Marine Pollution Bulletin, 2025)

Condition assessment of corroded spanning subsea pipelines under vortex-induced vibration - Xinhong Li; Runquan Li; Yaping Hu; Ziyue Han; Xiuquan Liu; Yuanjiang Chang (Ocean Engineering, 2025)

Solid-phase microextraction with recessed matrix compatible coating for in situ sampling of per- and polyfluoroalkyl substances in meat - Yaping Li; Wei Zhou; Runshan Will Jiang; Janusz Pawliszyn (Food Chemistry, 2025)

Glyphosate exposure impairs glucose and lipid metabolism by disturbing the circadian clock system in mice liver - Bonan Xiao; Haizhen Jiang; Hao Dong; Chao Li; Haisen Zhang; Dengke Gao; Aihua Wang; Yaping Jin; Huatao Chen (Food and Chemical Toxicology, 2025)

Yield variation in early-maturing cotton in response to sowing dates and growing seasons is associated with differential resource utilization - Yadi Mi; Yaru Wang; Fengqi Wu; Yingchun Han; Beifang Yang; Yaping Lei; Shiwu Xiong; Xiaoyu Zhi; Yabing Li (European Journal of Agronomy, 2025)

Introducing transition metal cations to promote the oxygen reduction kinetics of double perovskite as SOFC cathode - Jie Yang; Yaping Zhang; Xiaofei Zhu; Jinghe Bai; Shangyu Li; Wenfu Yan; Defeng Zhou (Chemical Engineering Journal, 2025)

Density functional theory and machine learning method for the rapid screening of dual-atom catalysts in N2 electroreduction - Qingchen Li; Nan Xia; Yaping Zhu; Yan Gao; Yahui Liu; Haifeng Wang (Chemical Engineering Journal, 2025)

Corrigendum to “Porous liquids based on ZIF-67@ZIF-8 through the strategy of interface layer reconstruction for CO2 selective sorption” [Chem. Eng. J. 500 (2024) 156655] - Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Zhiye Du; Jingwen Wang; Libing Qian; Shuangshuang Long; Zicheng Wei; Wendi Fan; Jinwen Fan; Yunpan Ying; et al. (Chemical Engineering Journal, 2025)

Does urbanization of tourism-oriented cities promote urban ecological resilience? Observations, judgments, and verifications - Yaping Zhang; Jianjun Zhang; Yuhuan Geng; Shidong Liu; Kexin Yi; Mingyu Meng; Yufei Li (Journal of Geographical Sciences, 2025)

Targeting Nrf2 by bioactive peptides alleviate inflammation: expanding the role of gut microbiota and metabolites - Zhongxing Chu; Lingfeng Zhu; Yaping Zhou; Feiyan Yang; Zuomin Hu; Yi Luo; Wen Li; Feijun Luo (Critical Reviews in Food Science and Nutrition, 2025)

Eutrophication mitigates Cu-induced inhibition on growth and photosynthetic performance in the marine diatom Thalassiosira weissflogii - Shumin Zeng; Xiangyu Li; Linrong Peng; Juntian Xu; Zhenzhen Li; Yaping Wu (Marine Pollution Bulletin, 2025)

Zwitterionic-based hybrid monoliths for capillary microextraction of polypeptides in dairy products - Xiaoyun Lei; Yaping Jiang; Yang Li; Yanping Duan; Ting Guo; Tianlei Zhang; Zuoping Zhao; Huiping Dai; Xiaohui Ji (Food Chemistry, 2025)

ICPINN: Integral conservation physics-informed neural networks based on adaptive activation functions for 3D blood flow simulations - Youqiong Liu; Li Cai; Yaping Chen; Qixing Chen (Computer Physics Communications, 2025)

Synthesis of a novel tricarboxylic acid monomer and construction of branched polybenzimidazole membranes for vanadium redox flow battery - Huiting Li; Jun Long; Wenheng Huang; Xiyang Liu; Jinchao Li; Liang Chen; Qin Chen; Qianqian Liang; Zhengjin Yang; Yaping Zhang (Chemical Engineering Journal, 2025)

Biochar and PGPR Influence Rhizosphere Bacteria and Synergistically Regulate Tomato Seedling Biomass Under Greenhouse Conditions - Zhenlu Yan; Yuyuan Xing; Changli Ma; Xin Li; Yaping Duan; Xue Wang; Minghao Liu; Muhammad Khashi u Rahman; Xingang Zhou (Journal of Soil Science and Plant Nutrition, 2025)

Quantitative climate reconstruction of the Mid- to late Holocene based on pollen records from Northern Shandong, China - Yaping Li; Wenhao Zheng; Wenfei Liu; Kai Su; Wei Liu; Junna Zhang; Kai Ning; Zhenjing Yang; Guiyun Jin (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Role of HSP40 proteins in genome maintenance, insulin signaling and cancer therapy - Yaping Huang; Guo-Min Li (DNA Repair, 2025)

Simulated characteristics of estuarine fronts in the Changjiang River Delta - Qing Tian; Yaping Wang; Jianrong Zhu; Weihua Li (Journal of Oceanology and Limnology, 2025)

Establishment of different artificial infection method models for grass carp reovirus - Hanyue Wang; Yongming Li; Qian Wang; Bin Gui; Lanjie Liao; Zuoyan Zhu; Yaping Wang; Rong Huang; Libo He (Aquaculture, 2025)

Vegetation and climate dynamics in Southwestern China during the Han and Jin Dynasties (202 BC-AD 420): Insights from the Spore-pollen and hydrological records from the Chengba site - Junna Zhang; Liu Qi; Yaping Li; Weidong Chen; Luhong Zheng; Xueran Wang; Songhan Li; Bingyuan Zhang (Quaternary International, 2025)

CmERFIV-4-CmWRKY44-CmPSY1 modulates ethylene-induced β-carotene accumulation in oriental melon fruit - Fei Luo; Xiaoyu Duan; Ge Gao; Yaping Zhao; Meng Li; Hongyan Qi (Postharvest Biology and Technology, 2025)

Fermentation of soymilk by strains with high conversion ability to soy isoflavones: Strain screening, flavor characteristics, antioxidant properties, and in vitro digestion - Yaping Zheng; Kaiqi Gao; Zimu Li; Yinzhi Zhang; Xuejian Li; Wei Zhang; Ling Guo; Yu Zhang; Yujun Jiang (Food Bioscience, 2025)

Role of Bacillus atrophaeus B1 in gut on nicotine tolerance of the fall armyworm - Yaping Chen; Wenyuan Zhao; Yanfang Hu; Yao Chen; Yahong Li; Zhongxiang Sun; Yuerui Li; Rongchao Luo; Ewei Du; Furong Gui (Pesticide Biochemistry and Physiology, 2025)

Research on the spatial correlation network and its driving factors for synergistic development of pollution reduction, carbon reduction, greening, and growth in China's tourism industry - Ying Li; Shizhuan Hao; Yaping Liu; Beilei Chen; Tongqian Zou (Journal of Environmental Management, 2025)

A dual-functional monomer-based molecularly imprinted fluorescent aptasensor employing near-infrared carbon dots for selective detection of quinine in food - Xuyuan Sun; Hao Liu; Zhengyuan Dai; Ying Wang; Li Li; Yaping Ding (Food Chemistry, 2025)

Dynamic simulation of local acceptance of NIMBY facilities based on the RAS-Deffuant model: The influence of government and media information - Xin Wan; Rubing Wang; Xiaoyu Dong; Jiayue Wu; Yaping Zheng; Qian Li (Environmental Impact Assessment Review, 2025)

Recent advances in fucoidan-based improved delivery systems: Structure, carrier types and biomedical applications - Haifu Jia; Yuanyuan Li; Yaping Zheng; Huabing Wang; Feng Zhao; Xinyan Yang; Qianyu Zhao; Yujun Jiang; Chaoxin Man (Carbohydrate Polymers, 2025)

Hereditary non-spherocytic hemolytic anemia with GPI mutations successfully treated with allogeneic hematopoietic stem cell transplantation: a first report of two cases - Huimin Li; Jiali Wang; Liucheng Rong; Jian Li; Yao Xue; Yongjun Fang; Yaping Wang (Journal of Molecular Medicine, 2025)

Soil micro-food web composition determines soil fertility and crop growth - Yaping Lin; Qing Yi; Dandan Gao; Jiangnan Li; Wei Zhang; Kelin Wang; Dan Xiao; Peilei Hu; Jie Zhao (Soil Ecology Letters, 2025)

Rainfall intensities determine accuracy of canopy interception simulation using the Revised Gash model - Mengliang Ma; Qiang Li; Yaping Wang; Jin Liang; Jiangyao Wang; Jinliang Liu; Mingfang Zhang (Agricultural and Forest Meteorology, 2025)

Comparative analysis of Seabuckthorn and its significant component in enhancing fish mucosal immunity - Yuhang Liu; Lian Su; Danying Cao; Nan Wu; Yuhang Hu; Fatima Altaf; Jialin Li; Qingsong Zhu; Junheng Liu; Qianqian Zhang; Haokun Liu; Yingyin Cheng; et al. (Aquaculture, 2025)

Seismic geomorphology and reservoir conditions of a Middle Miocene submarine channel system in the Taranaki basin, New Zealand - Guangxu Wang; Wei Wu; Quan Li; Weiqing Liu; Yongsheng Zhou; Shiqin Liang; Yaping Sui (Marine and Petroleum Geology, 2025)

Multifunctional bilayer electrocatalytic membrane with high permeability and antifouling property for efficient removal of dye from water - Yuan Zhu; Gege Zhao; Tianqi Du; Miao Zhang; Chengcheng Li; Xing Su; Yating Ji; Zaisheng Cai; Yaping Zhao (Journal of Water Process Engineering, 2025)

Quality differences in sea buckthorn (Hippophaë rhamnoides L.) berries of major varieties in China based on key components and antioxidant activity - Yaping Zheng; Kangmeng Sun; Xinyuan Sun; Yue Li; Peigen Xiao; Chunnian He (Food Chemistry, 2025)

The 2-aminoadipic acid (2-AAA) regulates grass carp ULK2 to inhibit GCRV replication - Xinyu Liang; Xuyang Wang; Xiaowen Zou; Qian Wang; Hanyue Wang; Cheng Yang; Yongming Li; Lanjie Liao; Zuoyan Zhu; Yaping Wang; Libo He (Fish & Shellfish Immunology, 2025)

A new evolutionary topology optimization method for truss structures towards practical design applications - Yaping Lai; Qi Cai; Yu Li; Jiayong Chen; Yi Min Xie (Engineering Structures, 2025)

Boosting electrocatalytic performance of BaPrO3-δ −based cathode catalysts by Co and Ni co-doping for protonic ceramic fuel cells - Bo Liu; Yanping Zheng; Xinwei Yang; Yaping Liu; Dong Yan; Jian Li; Lichao Jia (Chemical Engineering Journal, 2025)

Landscape indices explain different responses of runoff and sediment yield to land use/cover change on the Loess Plateau, China - Yanli Qin; Peng Shi; Yuan Hu; Qiang Li; Yaping Wang; Qiaoqiao Wang; Duoduo Zhou (CATENA, 2025)

Associations Between Organophosphate Esters Exposure and Metabolic Syndrome: Exploring the Mediating Role of Oxidative Stress and Inflammation in Adults - Sijie Yang; Yaping Li; Ling Liu; Zhengce Wan; Qitong Xu; Chang Xie; Lulu Song; Youjie Wang; Hui Chen; Surong Mei (Exposure and Health, 2025)

Comparative investigation on the adsorption behavior of bromate in aqueous solutions using Zn/Ni/Al-LDH and Ni/Al-LDH: optimization, equilibrium analysis, and mechanistic insights - Yaping Qin; Huixue Ren; Shengyun Jiang; Yuxin Bi; Chuntong Li; Rui Fang (Journal of Environmental Health Science and Engineering, 2025)

Efficiently catalytic purification of indoor formaldehyde upon Co-N sites derived from ZIF-67 carbonization - Zhaoying Di; Runduo Zhang; Xiaonan Guo; Hanxiao Shen; Sebastien Royer; Jingbo Jia; Ying Wei; Yaping Li; Lirong Zheng (Fuel, 2025)

Gold nanoparticle-catalyzed oxidative esterification of furfural: Enhancement by NaOH-etched γ-Al2O3 support - Xianjie Li; Bingxiao Feng; Hailin Zhang; Yaping Liu; Meng Xiao; Tingting Huang; Quanhong Zhu; Hongbing Song (Fuel, 2025)

A flexible humidity-resistant nanofiber-based triboelectric nanogenerator with high electrical output stability as self-powered sensors for motion monitoring - Yue Sun; Zicheng Qian; Yuna Wang; Yaping Li; Yide Zheng; Yong Liu (Chemical Engineering Journal, 2025)

High lead-tolerant mutant Bacillus tropicus AT31-1 from rhizosphere soil of Pu-erh and its remediation mechanism - Qiang Li; Wenxia Yuan; Xiujuan Deng; Yaping Chen; Limei Li; Lijiao Chen; Raoqiong Che; Wei Huang; Yamin Wu; Chun Wang; Zejun Wang; Miao Zhou; et al. (Bioresource Technology, 2025)

Rice rhizosphere microbiome is more diverse but less variable along environmental gradients compared to bulk soil - Yaping Guo; Yakov Kuzyakov; Na Li; Bin Song; Zihao Liu; Jonathan M. Adams; Lin Yang (Plant and Soil, 2025)

Peanut–cotton intercropping to enhance soil ecosystem multifunctionality: Roles of microbial keystone taxa, assembly processes, and C-cycling profiles - Shijie Zhang; Yingchun Han; Guoping Wang; Lu Feng; Yaping Lei; Shiwu Xiong; Beifang Yang; Xiaoyu Zhi; Minghua Xin; Yahui Jiao; Xiao-Fei Li; Yabing Li; et al. (Agriculture, Ecosystems & Environment, 2025)

Effect of long-term temperature-controlled rearing on growth traits and sexual maturity of common carp (Cyprinus carpio) - Yongming Li; Kuangxin Chen; Bin Gui; Cheng Yang; Libo He; Lanjie Liao; Zuoyan Zhu; Yaping Wang; Rong Huang (Aquaculture, 2024)

Occurrence and distribution of atrazine in groundwater from agricultural areas in China - Shengpin Li; Fuyang Huang; Haitao Piao; Wenpeng Li; Fei Liu; Qianying Zhu; Yaping He; Jialin Wang; Maohua Yan (Science of The Total Environment, 2024)

Association between blood microplastic levels and severity of extracranial artery stenosis - Hongxiang Yu; Hongxia Li; Can Cui; Yingying Han; Yaping Xiao; Bei Zhang; Gang Li (Journal of Hazardous Materials, 2024)

The alleviating effects and mechanisms of Lactiplantibacillus plantarum MC14 on hyperuricemia in mice - Jie Xiong; Jia-Juan Wu; Dong-mei Liu; Muhammad Yousaf; Liu-Jun Liu; Suping Zeng; Qinqin Li; Jun Tang; Yaping Wu (Food Bioscience, 2024)

The association of organochlorine pesticides and polychlorinated biphenyls exposure with dyslipidemia and blood lipids: The mediating effect of white blood cell counts - Mingye Zhang; Lipan Wang; Xiang Li; Limei Wang; Yaping Li; Sijie Yang; Lulu Song; Zhengce Wan; Yongman Lv; Youjie Wang; Surong Mei (Environmental Pollution, 2024)

Multi-protection durable unidirectional water-transport fabric with personalized moisture and thermal management - Gege Zhao; Yuan Zhu; Tianqi Du; Miao Zhang; Chengcheng Li; Xing Su; Zaisheng Cai; Yaping Zhao (Chemical Engineering Journal, 2024)

Multi-functional graphene aerogels/epoxy resin composites with Janus structure for enhanced electromagnetic interference shielding - Zhongjie He; Xiaoqian Li; Weirui Zhang; Xiaoyu Cheng; Mingzhong Wang; Wenjing Lu; Dongdong Yao; Yaping Zheng; Jiahe Liang (Chemical Engineering Journal, 2024)

Association Between Neuroinflammation and Parkinson’s Disease: A Comprehensive Mendelian Randomization Study - YiNi Wang; XinYu Shi; YaPing Yin; Fei Yang; YiNan Zhang; Xin He; Da Wen; Bai-Xiang Li; Kun Ma (Molecular Neurobiology, 2024)

Effects of 2,4,6-Trichloroanisole on the morphological development and motility of zebrafish - Yanxia Zuo; Fang Zhou; Rong Huang; Zhihui Jia; Juhong Xie; Guangxin Wang; Shuzhao Jia; Yongming Li; Manyi Wang; Lanjie Liao; Feng Ge; Yaping Wang (Science of The Total Environment, 2024)

ZnO nanoparticles induce melanoma-like lesions via recruiting dermal dendritic cells in barrier-damaged skin in mice - Menghan You; Yingying Huang; Yeda Chen; Dan Li; Yaping Tang; Yi kuan Du; Hong Yang; Anfa Liang; Guodong Hu; Yinghua Chen (Food and Chemical Toxicology, 2024)

Porous liquids based on ZIF-67@ZIF-8 through the strategy of interface layer reconstruction for CO2 selective sorption - Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Zhiye Du; Jingwen Wang; Libing Qian; Shuangshuang Long; Zicheng Wei; Wendi Fan; Jinwen Fan; Yunpan Ying; et al. (Chemical Engineering Journal, 2024)

Rill erosion and controlling factors on highway side-slopes in the permafrost region - Rui Li; Lilei Wu; Longxi Cao; Yaping Kong; Guo Chen; Ting Wu (Journal of Mountain Science, 2024)

Multi-omics analysis reveals anthocyanin synthesis is associated with drought stress tolerance in Chaenomeles speciosa flowers - Shuangyu Zhang; Xiling Chen; Yanshen Ren; Xingyue Xue; Yaping Xu; Qi Wang; Yanru Xie; Tengxun Zhang; Jiayi Lin; Xiaolu Chen; Houhua Li (Journal of Cleaner Production, 2024)

The nature of synergy effects between VO and TiO2 in low temperature NH3-SCR reaction - Yingying Jin; Jiaying Li; Kaihao Fan; Yong Chen; Yaping Yang; Xuesong Liu (Journal of Environmental Chemical Engineering, 2024)

The influences of extraction methods on the chemical constituents of Lyonia ovalifolia (wall.) Drude and intracellular protective effects based on metabolomics analysis - Chunyan Li; Mengcheng Li; Zhenhao Zhao; Afsar Khan; Tianrui Zhao; Yaping Liu; Zhengxuan Wang; Guiguang Cheng (Food Chemistry, 2024)

Widely metabolomic combined with transcriptome analysis to build a bioactive compound regulatory network for the fruit growth cycle in Pseudocydonia sinensis - Shuangyu Zhang; Yang Wu; Yanshen Ren; Yaping Xu; Hong An; Qianyi Zhao; Yu Wang; Houhua Li (Food Chemistry, 2024)

Assessment of uric acid-lowering activity, safety and stress tolerance of Lactiplantibacillus plantarum MC14 based on whole gene sequencing and phenotyping experiments - Jie Xiong; Lingxing Feng; Muhammad Yousaf; Suping Zeng; Jun Tang; Yaping Wu; Qinqin Li; Dong-mei Liu (Food Bioscience, 2024)

Deep eutectic solvent microemulsions with abundant hydrogen ions in supercritical CO2 for decontamination of radioactive solid waste: Overcoming roadblocks to hydrogen ions deficiency - Huitao Lv; Jianzhang Gao; Jiaqi Chen; Tianyu Li; Chao Peng; Yaping Li; Fuqiu Ma; Yun Xue; Yongde Yan; Emmanuel Osei Tutu (Chemical Engineering Journal, 2024)

A novel “pore-carrier transfer” strategy for preparation of porous liquids toward efficient CO2 capture - Yangyang Xin; Dechao Wang; Weirui Zhang; Fangfang Su; Jing Zhang; Yisong Liu; Wendi Fan; Xiaoqian Li; Libing Qian; Dongdong Yao; Yaping Zheng (Chemical Engineering Journal, 2024)

Different contributions of meteorological conditions and emission reductions to the ozone pollution during Shanghai’s COVID-19 lockdowns in winter and spring - Xuedan Dou; Mengying Li; Yaping Jiang; Zhe Song; Pengfei Li; Shaocai Yu (Atmospheric Pollution Research, 2024)

Mechanism of probiotics in the intervention of colorectal cancer: a review - Qinqin Li; Dongmei Liu; Minghua Liang; Yichao Zhu; Muhammad Yousaf; Yaping Wu (World Journal of Microbiology and Biotechnology, 2024)

SNCA is a potential therapeutic target for COVID-19 infection in diffuse large B-cell lymphoma patients - Can Chen; Yun Li; Yiwei Li; Zhenzhen Chen; Pengfei Shi; Yaping Xie; Shenxian Qian (Apoptosis, 2024)
Cuprotosis related genes (CRGs) have been proved to be potential therapeutic targets for coronavirus disease 2019 (COVID-19) and cancer, but their immune and molecular mechanisms in COVID-19 infection in Diffuse Large B-cell Lymphoma (DLBC/DLBCL) patients are rarely reported. Our research goal is first to screen the key CRGs in COVID-19 through univariate analysis, machine learning and clinical samples. Secondly, we determined the expression and prognostic role of key CRGs in DLBCL through pan-cancer analysis. We validated the expression levels and prognosis using multiple datasets and independent clinical samples and validated the functional role of key CRGs in DLBCL through cell experiments. Finally, we validated the expression levels of CRGs in COVID-19 infected DLBCL patients samples and analyzed their common pathways in COVID-19 and DLBCL. The results show that synuclein-alpha (SNCA) is the common key differential gene of COVID-19 and DLBCL. DLBCL cells confirm that high expression of SNCA can significantly promote cell apoptosis and significantly inhibit the cycle progression of DLBCL. High expression of SNCA can regulate the binding of major histocompatibility complexes (MHCs) and T cell receptor (TCR) by regulating immune infiltration of Dendritic cells, effectively enhancing T cell-mediated anti-tumor immunity and clearing cancer cells. In conclusion, SNCA may be a potential therapeutic target for COVID-19 infection in DLBCL patients. Our study provides a theoretical basis for improving the clinical treatment of COVID-19 infection in DLBCL patients.

Synthesis of P-Rich Carbon Quantum Dots for Sensitive Fluorescent Detection of 2-Methylimidazole - Zhengyuan Dai; Hao Liu; Xuyuan Sun; Ying Wang; Jie Fan; Li Li; Yaping Ding (Journal of Fluorescence, 2024)

Role of Enterococcus mundtii in gut of the tomato leaf miner (Tuta absoluta) to detoxification of Chlorantraniliprole - Yao Chen; Yaping Chen; Yibo Zhang; Zhongxiang Sun; Yahong Li; Jiasheng Ding; Guifen Zhang; Ewei Du; Xiaoyan Zi; Chaoxin Tian; Wenyuan Zhao; Furong Gui (Pesticide Biochemistry and Physiology, 2024)

Biochar with KMnO4-hematite modification promoted foxtail millet growth by alleviating soil Cd and Zn biotoxicity - Xirui Kang; Na Geng; Yaping Li; Wei He; Hui Wang; Hong Pan; Quangang Yang; Zhongchen Yang; Yajie Sun; Yanhong Lou; Yuping Zhuge (Journal of Hazardous Materials, 2024)

Corrigendum to “Distribution of organophosphorus pesticides and its potential connection with probiotics in sediments of a shallow freshwater lake” [Journal of Contaminant Hydrology 261 (2024) 104306] - Yanping Hu; Rong Xiao; Yaping Wang; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Javiera Manquian; Wenbin Pan (Journal of Contaminant Hydrology, 2024)

Accumulation and ecological risk assessment of diazinon in surface sediments of Baiyangdian lake and its potential impact on probiotics and pathogens - Yaping Wang; Rong Xiao; Yanping Hu; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Wenbin Pan (Environmental Pollution, 2024)

Thiophene-containing conjugated polymers modified Zn0.5Cd0.5S inorganic/organic S-scheme heterojunction for boosting photocatalytic hydrogen production coupled with benzyl alcohol oxidation - Lele Wei; Ru Song; Jiarui Song; Yaping Li; Yina Nie; Lin Liu; Jun Wan (Chemical Engineering Journal, 2024)

Latent heat type nanofluid based on MXene and MoS2 modified hierarchical structured phase change nanocapsules for sustainable and efficient light-heat conversion - Fangfang Su; Xiaoqian Li; Zhongjie He; Jinliang Xie; Weirui Zhang; Yangyang Xin; Xiaoyu Cheng; Dongdong Yao; Yaping Zheng (Chemical Engineering Journal, 2024)

Analysis of the Relationship Between Parkinson’s Disease and Diabetic Retinopathy Based on Bioinformatics Methods - XinYu Shi; YiNi Wang; YaPing Yin; Fei Yang; YiNan Zhang; Xin He; Da Wen; Kun Ma; Bai-Xiang Li (Molecular Neurobiology, 2024)

Corrigendum to “Pathogen profile of Baiyangdian Lake sediments using metagenomic analysis and their correlation with environmental factors” [Sci. Total Environ. 913 (2024) 169628] - Rong Xiao; Yanping Hu; Yaping Wang; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Jacquelinne J. Acuña; Wenbin Pan (Science of The Total Environment, 2024)

Mid to late Holocene climate changes and grazing activities in northern Loess Plateau, China - Yaping Zhang; Guilin Zhang; Keliang Zhao; Jian Wang; Marika Vicziany; Xinying Zhou; Xiaoqiang Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Effects of nanoplastic exposure during pregnancy and lactation on neurodevelopment of rat offspring - Lei Tian; Yaping Zhang; Jiang Chen; Xuan Liu; Huipeng Nie; Kang Li; Huanliang Liu; Wenqing Lai; Yue Shi; Zhuge Xi; Bencheng Lin (Journal of Hazardous Materials, 2024)

Artificial phytoremediation solar interface evaporator for efficient heavy metal salt separation and saline soil remediation - Yaping Xu; Chenyang Dang; Xiangkun Elvis Cao; Yunteng Cao; Jiu Huang; Yuxiang Xu; Minghui Shan; Rui Liu; Peng Li; Guiyin Xu; Meifang Zhu (Journal of Environmental Chemical Engineering, 2024)

Individual and joint effects of organophosphate esters and hypertension or diabetes on renal injury among Chinese adults - Sijie Yang; Yaping Li; Mingye Zhang; Qitong Xu; Chang Xie; Zhengce Wan; Lulu Song; Yongman Lv; Youjie Wang; Hui Chen; Surong Mei (International Journal of Hygiene and Environmental Health, 2024)

Phytochemicals from the rhizome of Bletilla formosana and their antioxidant, cytoprotective and anti-inflammatory activities - Yiqian Li; Luya Qiu; Yifen Wang; Zhengxuan Wang; Guiguang Cheng; Yaping Liu (Food Bioscience, 2024)

Regional assessment for the occurrence probability of wind erosion based on the joint probability density function of air density and wind speed - Yushi Liang; Yaping Shen; Zeyu Zhang; Xiaodong Ji; Mulan Zhang; Yiran Li; Yu Wang; Xinyue Xue (CATENA, 2024)

Machine learning framework develops neutrophil extracellular traps model for clinical outcome and immunotherapy response in lung adenocarcinoma - A. Xuan Han; B. Yaping Long; C. Yao Li; D. Di Huang; E. Qi Xiong; F. Jinfeng Li; G. Liangliang Wu; Qiaowei Liu; G. Bo Yang; H. Yi Hu (Apoptosis, 2024)

Association between organophosphate esters individual and mixed exposure with the risk of hyperlipidemia and serum lipid levels among adults in Wuhan, China - Qitong Xu; Chang Xie; Sijie Yang; Yaping Li; Mingye Zhang; Zhengce Wan; Lulu Song; Yongman Lv; Hui Chen; Youjie Wang; Surong Mei (Environmental Science and Pollution Research, 2024)

Associations of exposure to organochlorine pesticides and polychlorinated biphenyls with chronic kidney disease among adults: the modifying effects of lifestyle - Chang Xie; Sijie Yang; Yaping Li; Mingye Zhang; Qitong Xu; Zhengce Wan; Lulu Song; Yongman Lv; Dan Luo; Qiang Li; Youjie Wang; Hui Chen; et al. (Environmental Science and Pollution Research, 2024)

Reduction of heavy metal emissions by adding modified attapulgite to sludge in bubbling fluidized bed incineration process - Zhiyao Li; Junfeng Pang; Yu Zhou; Kai Shen; Yaping Zhang (Fuel, 2024)

Microglial exosomes in paraquat-induced Parkinson's disease: Neuroprotection and biomarker clues - Jingwen Wu; Wenya Shao; Xu Liu; Fuli Zheng; Yaping Wang; Ping Cai; Zhenkun Guo; Hong Hu; Guangxia Yu; Jianhui Guo; Linlin Yao; Siying Wu; et al. (Environmental Pollution, 2024)

Interactive effects of urine components and treatment conditions on antibiotic degradation of combined system integrating thermally activated peroxydisulfate and membrane distillation using machine learning - Yaping Lyu; Zifu Li; Zhiling Guo; Iseult Lynch; Peng Zhang; Shikun Cheng (Chemical Engineering Journal, 2024)

Functional comparison of Rab3aa and Rab3ab in grass carp (Ctenopharyngodon idella) immune response and GCRV replication - Lifei Luo; Lv Xiong; Cheng Yang; Libo He; Lanjie Liao; Yongming Li; Zuoyan Zhu; Yaping Wang; Rong Huang (Aquaculture, 2024)

Spartina alterniflora invasion benefits blue carbon sequestration in China - Jingfan Zhang; Dehua Mao; Jihua Liu; Yaping Chen; Matthew Kirwan; Christian Sanders; Jinge Zhou; Zhe Lu; Guoming Qin; Xingyun Huang; Hui Li; Hengqi Yan; et al. (Science Bulletin, 2024)

Empirical investigation of parameter impacts on the three-dimensional coefficient of restitution of jujube at the time of harvest - Shiqi Yao; Shiguan An; Zhiye Bai; Shan Chen; Za Kan; Hewei Meng; Li Yaping (Postharvest Biology and Technology, 2024)

Radiation source terms analysis and classification of radioactive waste for the decommissioning of the first HWRR reactor in China - Yaping Guo; Peng Nie; Ruizhi Li; Lijun Zhang; Zelong Zhao (Environmental Science and Pollution Research, 2024)

Enhancing resource utilization: A novel method for effective separation of residual film and impurities in cotton fields - Bingcheng Zhang; Xinzhong Wang; Rongqing Liang; Jiali Li; Yaping Li; Za Kan; Hewei Meng (Journal of Environmental Management, 2024)

Efficient separation of cresol isomers using azeotropic coupling pressure-swing distillation: From separation mechanism to process integration - Chao Pan; Jingtao Guo; Yaping Liu; Bingxiao Feng; Guoxuan Li; Hengjun Gai; Hongbing Song; Meng Xiao; Tingting Huang; Quanhong Zhu (Fuel, 2024)

Increased overyielding probability and yield stability from a 5-year cotton-based intercropping - Yurui Tang; Yurong Qiu; Xin Li; Haoyue Qin; Jian Wang; Shijie Zhang; Yingchun Han; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Shiwu Xiong; et al. (European Journal of Agronomy, 2024)

Preferentially in-situ generated copper nanograins boosting fast kinetic conversion magnesium storage of bimetallic copper-cobalt sulfide cathode - Yaping Xia; Chunxiao Chen; Lin Ran; Hou-an Zhang; Shuai Cui; Panfei Xiao; Fei Xu; Daohong Zhang; Ting Li (Chemical Engineering Journal, 2024)

Flexible and wearable functional materials for ionizing radiation Protection: A perspective review - Hao Li; Linping Yan; Jibo Zhou; Yaping Wang; Xuepin Liao; Bi Shi (Chemical Engineering Journal, 2024)

An Advanced Molecularly Imprinted Photochemical Sensor Based Carbon Quantum dots for Highly Sensitive Detection of Chloramphenicol in Food - Hao Liu; Jing Yang; Xuyuan Sun; Peijie Wu; Guan Wang; Yan Huang; Li Li; Yaping Ding (Journal of Fluorescence, 2024)

Effects of transition-metal ions on the reduction of N-nitrosodimethylamine in water by zinc - Ying Han; Xiaoping Zheng; Beibei Jiang; Yuling Tang; Hongyuan Liu; Kemin Zhang; Yaping Guo; Jun Li (Journal of Environmental Chemical Engineering, 2024)

Optical sensors of volatile organic compounds for non-invasive diagnosis of diseases - Xiaoyun Qu; Yaping Hu; Chenggang Xu; Yue Li; Lin Zhang; Qiao Huang; Sareh Sadat Moshirian-Farahi; Jianmin Zhang; Xiahong Xu; Ming Liao; Yingchun Fu (Chemical Engineering Journal, 2024)

Chemically tailored molecular surface modification of bamboo pulp fibers for manipulating the electret performance of electret filter media - Chunxia Pang; Huanhuan You; Sijie Lei; Fan Su; Lili Liang; Zhanguo Li; Xiaoyan Lin; Yaping Zhang; Hao Zhang; Xunhai Pan; Yang Hu (Carbohydrate Polymers, 2024)

High spatiotemporal asynchrony between water deficit and nitrate accumulation under apple orchards in deep loess deposits - Wangjia Ji; Yaping Wang; Ruifeng Li; Wenzhao Liu; Zhi Li (CATENA, 2024)

Artificial infection pathway of largemouth bass LMBV and identification of resistant and susceptible individuals - Ya Zhang; Bin Gui; Zhihui Jia; Yongming Li; Lanjie Liao; Zuoyan Zhu; Yaping Wang; Rong Huang (Aquaculture, 2024)

LncRNA STAT3-AS regulates endometrial receptivity via the STAT3 signaling pathway - Yanni Jia; Wei Wang; Jiaqi Jiang; Xinyan Zhang; Haijing Li; Suhua Gong; Zuhui Li; Haokun Liu; Chunmei Shang; Aihua Wang; Yaping Jin; Pengfei Lin (Theriogenology, 2024)

The shape of reactive nitrogen losses from intensive farmland in China - Xiaoying Zhan; Qingwen Zhang; Ming Li; Xikang Hou; Ziyin Shang; Zhen Liu; Yaping He (Science of The Total Environment, 2024)

Long-term liming mitigates the positive responses of soil carbon mineralization to warming and labile carbon input - Qiong Xiao; Wenju Zhang; Lei Wu; Yaping Huang; Zejiang Cai; Dongchu Li; Xingliang Xu; Iain P. Hartley (Journal of Environmental Management, 2024)

Oxidative esterification of 5-hydroxymethylfurfural to dimethyl 2,5-furandicarboxylate over Au-supported poly(ionic liquid)s - Yaping Liu; Chao Pan; Xiaomin Qiu; Xianjie Li; Hengjun Gai; Meng Xiao; Tingting Huang; Quanhong Zhu; Hongbing Song (Fuel, 2024)

Grass carp peroxiredoxin 5 and 6-mediated autophagy inhibit grass carp reovirus replication and mitigate oxidative stress - Qian Wang; Xinyu Liang; Hanyue Wang; Cheng Yang; Yongming Li; Lanjie Liao; Zuoyan Zhu; Yaping Wang; Libo He (Fish & Shellfish Immunology, 2024)

Cracking formation and evolution in surrounding rock of a deep fractured rock mass roadway: A study of the 790-m level segment engineering at the Jinchuan Mine, China - Xiaojun Yu; Yaping Yang; Xifan Li; Huanzhen Luo; Yushan Wang; Xizhi Zhang; Yongyuan Kou; Hongye Li; Yangyi Zhou (Engineering Geology, 2024)

A numerical study on the collection efficiency of devices for atmospheric dust deposition - Kang Gong; Jie Zhang; Ning Huang; Yaping Shao; Xuanmin Li (CATENA, 2024)

Description of Microbacterium dauci sp. nov., a plant growth hormone indoleacetic acid-producing and nitrogen-fixing bacterium isolated from carrot rhizosphere soil - Jiawen Zheng; Yunyu Liao; Yang Li; Dongsheng Li; Yaping Sun; Zijun Xiao (Archives of Microbiology, 2024)

Sinomenine improves resistance to foodborne enteritis and Anti-bacteria mucosal immunity in grass carp - Yuhang Liu; Danying Cao; Nan Wu; Xuyang Zhao; Qingsong Zhu; Lian Su; Fatima Altaf; Qianqian Zhang; Haokun Liu; Yongming Li; Bruno Hamish Unger; Yingyin Cheng; et al. (Aquaculture, 2024)

Baicalin − 2- ethoxyethyl ester alleviates renal fibrosis by inhibiting PI3K/AKT/NF-κB signaling pathway - Jiacun Li; Ke Zhang; Mei Xu; Huanyue Cui; Yaping Guo; Dahong Yao; Wenhua Chen; Huaimin Liang; Hangyu Wang; Jinhui Wang (Toxicology and Applied Pharmacology, 2024)

Different ligand functionalized bimetallic (Zr/Ce)UiO-66 as a support for immobilization of phosphotungstic acid with enhanced activity for the esterification of fatty acids - Qiuyun Zhang; Yaping Wu; Xingyue Hong; Zhenying Li; Yanting Lei; Rongfei Yu; Taoli Deng; Yutao Zhang; Peihua Ma (Sustainable Chemistry and Pharmacy, 2024)

Pathogen profile of Baiyangdian Lake sediments using metagenomic analysis and their correlation with environmental factors - Rong Xiao; Yanping Hu; Yaping Wang; Junming Li; Congling Guo; Junhong Bai; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Jacquelinne J. Acuña; Wenbin Pan (Science of The Total Environment, 2024)

Large contributions of emission reductions and meteorological conditions to the abatement of PM2.5 in Beijing during the 24th Winter Olympic Games in 2022 - Yaping Jiang; Shaocai Yu; Xue Chen; Yibo Zhang; Mengying Li; Zhen Li; Zhe Song; Pengfei Li; Xiaoye Zhang; Eric Lichtfouse; Daniel Rosenfeld (Journal of Environmental Sciences, 2024)

Distribution of organophosphorus pesticides and its potential connection with probiotics in sediments of a shallow freshwater lake - Yanping Hu; Rong Xiao; Yaping Wang; Junming Li; Congling Guo; Junhong Bai; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Javiera Manquian; Wenbin Pan (Journal of Contaminant Hydrology, 2024)

Recovery and reuse of spent lithium-ion batteries as catalysts for low-temperature NH3-SCR - Na Wu; Mengtao Li; Qiao Zhang; Gang Xue; Yaping Wang; Cairong Gong (Chemical Engineering Journal, 2024)

Probiotic Potential of Bacillus amyloliquefaciens Isolated from Tibetan Yaks - Yuanyuan He; Feiran Li; Wenqian Zhang; Miao An; Aoyun Li; Yaping Wang; Yan Zhang; Muhammad Fakhar-e-Alam Kulyar; Mudassar Iqbal; Jiakui Li (Probiotics and Antimicrobial Proteins, 2024)

RETRACTED ARTICLE: Carnosic acid nanocluster-based framework combined with PD-1 inhibitors impeded tumorigenesis and enhanced immunotherapy in hepatocellular carcinoma - Wenhua Wu; Yaping Li; Xiaokang Wu; Junrong Liang; Weiming You; Xinyuan He; Qinhui Feng; Ting Li; Xiaoli Jia (Functional & Integrative Genomics, 2024)

Long-term manuring facilitates glomalin-related soil proteins accumulation by chemical composition shifts and macro-aggregation formation - Hongbo Yang; Qiong Xiao; Yaping Huang; Zejiang Cai; Dongchu Li; Lei Wu; Jeroen Meersmans; Gilles Colinet; Wenju Zhang (Soil and Tillage Research, 2024)

Microbial interaction patterns and nitrogen cycling regularities in lake sediments under different trophic conditions - Ziwei Wang; Xiaohong Ruan; Rongfu Li; Yaping Zhang (Science of The Total Environment, 2024)

Quaternary stratigraphic architecture of the Pearl River Mouth continental shelf, northern South China Sea: Unraveling stratigraphic imprints of tectonism, paleoceanography, and climate change - Haiteng Zhuo; Xin Nie; Ming Su; Wei Zhou; Yaping Lei; Yingmin Wang; Xuechao Peng; Yan Qiu; Weiyao Yan; Li'e Lin (Sedimentary Geology, 2024)

Does biogas industrial policy promote the industrial transformation? - Erga Luo; Ru Yan; Yaping He; Zhen Han; Yiyu Feng; Wenrong Qian; Jinkai Li (Resources Policy, 2024)

Enhanced peroxymonosulfate activation via heteroatomic doping defects of pyridinic and pyrrolic N in 2D N‑doped carbon nanosheets for BPA degradation - Guojuan Qu; Peng Jia; Shuai Tang; Md. Nahid Pervez; Yixiong Pang; Bin Li; Chengjin Cao; Yaping Zhao (Journal of Hazardous Materials, 2024)

Selective recovery of lithium from high-aluminum fly ash by using alkali-dissolution-assisted HBTA–TOPO synergistic extraction - Mingfei Xing; Fan Zhang; Pengyong Zheng; Yaping Wang; Li Zhao; Chuanyang Xu (Journal of Cleaner Production, 2024)

Infection of postharvest pear by Penicillium expansum is facilitated by the glycoside hydrolase (eglB) gene - Meiqiu Xu; Esa Abiso Godana; Jingyu Li; Yaping Deng; Yufei Ma; Huiyuan Ya; Hongyin Zhang (International Journal of Food Microbiology, 2024)

Effect of ferric ions on Cronobacter sakazakii growth, biofilm formation, and swarming motility - Yang Wang; Na Ling; Yaping Wang; Dexin Ou; Zhao Liang; Guoqing Li; Hongyuan Zhao; Yingwang Ye (International Journal of Food Microbiology, 2024)

Fisetin, a dietary flavonoid, promotes transintestinal cholesterol excretion through the activation of PPARδ - Yao Guo; Bing Liu; Yaping Geng; Ke Chen; Junyan Li; Xiangju Yin; Shenshen Zhang (Food Research International, 2024)

Reproductive hormones, organophosphate esters and semen quality: Exploring associations and mediation effects among men from an infertility clinic - Yaping Li; Zhiyi Zheng; Dan Luo; Chong Liu; Sijie Yang; Yingjun Chen; Qian Hu; Wenqing Lu; Yixin Wang; Surong Mei (Environmental Research, 2024)

Calcium signal regulated carbohydrate metabolism in wheat seedlings under salinity stress - Ya Zhang; Dan Qiao; Zhe Zhang; Yaping Li; Shuqian Shi; Yingli Yang (Physiology and Molecular Biology of Plants, 2024)

Water deficit limits soil organic carbon sequestration under old apple orchards in the loess-covered region - Ruifeng Li; Yaping Wang; Wangjia Ji; Wenzhao Liu; Zhi Li (Agriculture, Ecosystems & Environment, 2024)

Purification and characterization of a glycoprotein from Sipunculus nudus and its immune-enhancing activity to RAW 264.7 macrophages - Xuli Lu; Yaping Dai; Shengtao Yang; Tengfei Fu; Yunxia He; Fanke Zeng; Tinghui Chen; Yupo Cao; Ruyi Li; Jihua Li; Wei Zhou (Food Research International, 2023)

Unprecedented early summer warming recorded in tree rings on the central eastern Tibetan Plateau over the past three centuries - Jiangfeng Shi; Hui Wang; Jinbao Li; Shiyuan Shi; Jiarui Xu; Yaping Zhang; Huayu Lu (Climate Dynamics, 2023)

Comparative analysis of the transcriptional responses of Acetilactobacillus jinshanensis BJ01 to organic acids - Weifang Liao; Yaping Li; Yuan Zhang; Yibin Yang; Tuanyuan Yang; Lihong Miao (Archives of Microbiology, 2023)

Tea polyphenols coated sodium alginate-gelatin 3D edible scaffold for cultured meat - Xiaohong Chen; Linzi Li; Lin Chen; Wei Shao; Yan Chen; Xiaojing Fan; Yaping Liu; Changbo Tang; Shijie Ding; Xinglian Xu; Guanghong Zhou; Xianchao Feng (Food Research International, 2023)

Synergetic effect on fouling alleviating of membrane distillation in urine resource recovery by thermally activated peroxydisulfate pretreatment - Yaping Lyu; Xiuwei Ao; Zongsu Wei; Shikun Cheng; Xiaoqin Zhou; Nana Liu; Xuemei Wang; Rui Feng; Zifu Li (Environmental Research, 2023)

Directly linking plant N, P and K nutrition to biomass production in cotton-based intercropping systems - Yurong Qiu; Xin Li; Yurui Tang; Shiwu Xiong; Yingchun Han; Zhanbiao Wang; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Wenli Du; Xiaoyu Zhi; et al. (European Journal of Agronomy, 2023)

Synergistic activation of peroxymonosulfate by intrinsic defect and graphitic N of N, P co-doped carbon microspheres for BPA degradation - Guojuan Qu; Peng Jia; Tao Zhang; Shuai Tang; Md. Nahid Pervez; Yixiong Pang; Bin Li; Chengjin Cao; Yaping Zhao (Chemical Engineering Journal, 2023)

Research progress on pharmacological effects and mechanisms of cepharanthine and its derivatives - Liangliang Shi; Shuaizhe Wang; Shangzu Zhang; Jiawei Wang; Yaping Chen; Yangyang Li; Zhiwei Liu; Sichen Zhao; Benjun Wei; Liying Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

ALPK1 Expressed in IB4-Positive Neurons of Mice Trigeminal Ganglions Promotes MIA-Induced TMJ pain - Taomin Zhu; Huimin Li; Yuxiang Chen; Xueke Jia; Xiaohan Ma; Xin Liu; Yaping Feng; Jin Ke (Molecular Neurobiology, 2023)

Optimal operation strategy of peak regulation combined thermal power units and concentrating solar power plant with energy conversion and spinning reserve - Yunyun Yun; Dahai Zhang; Lixin Li; Yaping Li; Yiru Shi; Jinghan He (Journal of Cleaner Production, 2023)

Clean removal of silicon (IV) and vanadium (V) from high concentration chromium (VI) solutions in the chromate production processes - Xinqian Li; Bo Li; Yaping Dong; Zhengrong Niu; Dandan Gao; Haitao Feng; Wu Li (Journal of Cleaner Production, 2023)

Polyphenol zwitterionic nanohydrogel modified polyvinylidene difluoride membrane for separating oil-in-water emulsions with superior cycle stability - Yujia Tong; Yaping Zhang; Fiona Hammond Quarcoo; Changqing Miao; Xiao Xiao; Xiaohui Ju; Weixing Li (Journal of Environmental Chemical Engineering, 2023)

Effect of co-pyrolysis of sewage sludge with different plastics on the nitrogen, sulfur, and chlorine releasing characteristics and the heavy metals ecological risk of biochar - Jia Shen; Yan Wu; Guoxin Lan; Yaping Xia; Bin Yan; Yurong Li; Yuexin Zhang; Yue Yu; Chuan Fu; Anji Xu; Jie Zhou; Ailing Zhu; et al. (Journal of Environmental Chemical Engineering, 2023)

Soybean phenological changes in response to climate warming in three northeastern provinces of China - Minghua Xin; Zhenggui Zhang; Yingchun Han; Lu Feng; Yaping Lei; Xiaofei Li; Fengqi Wu; Jian Wang; Zhanbiao Wang; Yabing Li (Field Crops Research, 2023)

Establishment of a halotolerant bioremediation platform from Halomonas cupida using synthetic biology approaches - Wanwan Zhao; Weini Xiong; Yujie Liu; Hongfu Guo; Siqi Wang; Yaping Chen; Ruihua Liu; Bingzhi Li; Chao Yang (Chemical Engineering Journal, 2023)

The Secondary Motor Cortex-striatum Circuit Contributes to Suppressing Inappropriate Responses in Perceptual Decision Behavior - Jing Liu; Dechen Liu; Xiaotian Pu; Kexin Zou; Taorong Xie; Yaping Li; Haishan Yao (Neuroscience Bulletin, 2023)
The secondary motor cortex (M2) encodes choice-related information and plays an important role in cue-guided actions. M2 neurons innervate the dorsal striatum (DS), which also contributes to decision-making behavior, yet how M2 modulates signals in the DS to influence perceptual decision-making is unclear. Using mice performing a visual Go/No-Go task, we showed that inactivating M2 projections to the DS impaired performance by increasing the false alarm (FA) rate to the reward-irrelevant No-Go stimulus. The choice signal of M2 neurons correlated with behavioral performance, and the inactivation of M2 neurons projecting to the DS reduced the choice signal in the DS. By measuring and manipulating the responses of direct or indirect pathway striatal neurons defined by M2 inputs, we found that the indirect pathway neurons exhibited a shorter response latency to the No-Go stimulus, and inactivating their early responses increased the FA rate. These results demonstrate that the M2-to-DS pathway is crucial for suppressing inappropriate responses in perceptual decision behavior.

HIF-1α–PPARγ–mTORC1 signaling pathway-mediated autophagy induces inflammatory response in pancreatic cells in rats with hyperlipidemic acute pancreatitis - Yumei Ma; Xiaolin Li; Zhilan Liu; Xiaohong Xue; Yaping Wang; Yingcai Ma (Molecular Biology Reports, 2023)

Proteomic analysis of uterine lavage fluid of dairy cows at different time after delivery by mass spectrometry - Xingcan Jiang; Ziyuan Li; Xiyu Chang; Cong Huang; Rendong Qiu; Aihua Wang; Pengfei Lin; Keqiong Tang; Huatao Chen; Dong Zhou; Yaping Jin (Theriogenology, 2023)

Fine and coarse particulate air pollution and out-of-hospital cardiac arrest onset: a nationwide case-crossover study in China - Chang Pan; Chang Xu; Jiaqi Zheng; Ruixue Song; Chuanzhu Lv; Guoqiang Zhang; Huiqiong Tan; Yu Ma; Yimin Zhu; Xiaotong Han; Chaoqian Li; Shengtao Yan; et al. (Journal of Hazardous Materials, 2023)

A step closer to real practice: Integrated tandem photocatalysis-biofilm process towards degradation of crude oil - Xin Hu; Yaping Pan; Shanshan Zhao; Feifei Zhang; Fengshu Li; Zhe Li; Haoshuai Li; Yiming Li; Jinren Lu; Xiaolong Yang; Mutai Bao (Journal of Environmental Management, 2023)

Protective effect of hot-water and ethanol-aqueous extracts from Anneslea fragrans against acetaminophen-induced acute liver injury in mice - Yiwen Hu; Mengcheng Li; Yongpeng Wang; Qingwang Xue; Xiaodong Luo; Afsar Khan; Tianrui Zhao; Yaping Liu; Zhengxuan Wang; Yudan Wang; Guiguang Cheng (Food and Chemical Toxicology, 2023)

Fine lithospheric structure controlling Meso-Cenozoic tectono-magmatism in the South China Block: Inference from a multidisciplinary analysis - Feiyu Zhao; Yanhui Suo; Lijun Liu; Xianzhi Cao; Sanzhong Li; Suhua Jiang; Juzhi Deng; Mengxue Dai; Ying Liu; Yaping Hu; Shuzhong Sheng; Bin Hu (Earth-Science Reviews, 2023)

Facilitating photogenerated carrier transfer and water oxidation kinetics of BiVO4 photoanode via novel Zn@Co3C functional layer - Weibing Li; Liming Wang; Jie Zhou; Ning Wang; Xinyang Fu; Yibo Wang; Yuyu Bu; Yaping Zhang; Lei Wang (Chemical Engineering Journal, 2023)

Assessing Spatio-Temporal Variability of Soil Phosphorus in Different Cotton-Based Cropping Systems Using Geo-Statistics - Li Teng; Xiong Shiwu; Wang Zhanbao; Li Xiaofei; Han Yingchun; Wang Guoping; Lei Yaping; Feng Lu; Yang Beifang; Zhi Xiaoyu; Fan Zhengyi; Li Yabing (Journal of Soil Science and Plant Nutrition, 2023)

Visualize intracellular β-galactosidase using an asymmetric near-infrared fluorescent probe with a large Stokes shift - Shijun Chen; Xiaodong Ma; Haijie Wang; Lin Wang; Yuanyuan Wu; Yaping Wang; Yiyi Li; Wenkang Fan; Caoyuan Niu; Shicong Hou (Analytica Chimica Acta, 2023)

Manuring improves soil health by sustaining multifunction at relatively high levels in subtropical area - Xin Li; Lei Qiao; Yaping Huang; Dongchu Li; Minggang Xu; Tida Ge; Jeroen Meersmans; Wenju Zhang (Agriculture, Ecosystems & Environment, 2023)

Photo-aged non-biodegradable and biodegradable mulching film microplastics alter the interfacial behaviors between agricultural soil and inorganic arsenic - Shuai Tang; Peipei Sun; Guojuan Qu; Yue Tian; Junlai Liu; Md. Nahid Pervez; Xiuyan Li; Chengjin Cao; Yaping Zhao (Journal of Hazardous Materials, 2023)

Acceleration of Fe3+/Fe2+ cycle in garland-like MIL-101(Fe)/MoS2 nanosheets to promote peroxymonosulfate activation for sulfamethoxazole degradation - Ke Zhu; Wenlei Qin; Yaping Gan; Yizhe Huang; Zhiwei Jiang; Yuwen Chen; Xin Li; Kai Yan (Chemical Engineering Journal, 2023)

Dual-emitting cellulose nanocrystal hybrid materials with circularly polarized luminescence for anti-counterfeiting labels - Lingxiao Xing; Guihua Li; Yaping Sun; Xu Wang; Zaiwu Yuan; Yingjuan Fu; Menghua Qin (Carbohydrate Polymers, 2023)

Improved activity and significant SO2 tolerance of Sb–Pd–V oxides on N-doped TiO2 for CB/NO synergistic degradation - Guobo Li; Yaping Zhang; Peng Wu; Kai Shen; Shule Zhang; Shipeng Ding (Chemosphere, 2023)

A novel Q-learning based variable neighborhood iterative search algorithm for solving disassembly line scheduling problems - Yaxian Ren; Kaizhou Gao; Yaping Fu; Hongyan Sang; Dachao Li; Zile Luo (Swarm and Evolutionary Computation, 2023)

Rare earth element recovery and aluminum-rich residue production from high alumina fly ash by alkali pre-desilication enhance the mechanochemical extraction process - Mingfei Xing; Xiaofang Wu; Zixin Li; Fan Zhang; Yaping Wang; Li Zhao (Process Safety and Environmental Protection, 2023)

AraENCODE: A comprehensive epigenomic database of Arabidopsis thaliana - Zhenji Wang; Minghao Liu; Fuming Lai; Qiangqiang Fu; Liang Xie; Yaping Fang; Qiangwei Zhou; Guoliang Li (Molecular Plant, 2023)

Optimizing plant type structure to adjust the temporal and spatial distribution of water consumption and promote the growth and yield formation of cotton - Yaru Wang; Jiale Chen; Fengqi Wu; Beifang Yang; Yingchun Han; Lu Feng; Zhanbiao Wang; Xiaofei Li; Yaping Lei; Shiwu Xiong; Guoping Wang; Xiaoyu Zhi; et al. (European Journal of Agronomy, 2023)

Influencing mechanism and hydrogeological implications of water level fluctuation of lakes in the northern Qaidam Basin, Qinghai-Tibet Plateau - Yaping Cheng; Qishun Fan; Tianyuan Chen; Haotian Yang; Qingkuan Li; Chunmei Han (Journal of Oceanology and Limnology, 2023)

Dual recognition elements for selective determination of progesterone based on molecularly imprinted electrochemical aptasensor - Yan Huang; Daixin Ye; Jing Yang; Wenyi Zhu; Li Li; Yaping Ding (Analytica Chimica Acta, 2023)

Uncovering the dynamic evolution of microbes and n-alkanes: Insights from the Kuroshio Extension in the Northwest Pacific Ocean - Xin Hu; Xinping Wang; Shanshan Zhao; Lixin Cao; Yaping Pan; Fujuan Li; Fengshu Li; Jinren Lu; Yiming Li; Guodong Song; Honghai Zhang; Peiyan Sun; et al. (Science of The Total Environment, 2023)

Design of bifunctional TiO2-SSZ-13 mixed supports for potassium-resistant vanadia catalysts for NH3-SCR - Xuesong Liu; Yaping Yang; Jiaying Li; Yang Gao; Kaihao Fan; Yanghui Wang; Xintao Xu; Letong Yang; Xiaodong Wu (Fuel, 2023)

Corrigendum to ‘Polyvinyl alcohol/starch-based film incorporated with grape skin anthocyanins and metal-organic framework crystals for colorimetric monitoring of pork freshness ‘[Food Chem. 395 (2022) 133613] - Xueqi Lin; Ning Li; Qiao Xiao; Yaping Guo; Jie Wei; Tianhui Jiao; Qingmin Chen; Quansheng Chen; Xiaomei Chen (Food Chemistry, 2023)

Synergistic effects of combined treatment of 1,2-dichloroethane and high-dose ethanol on liver damage in mice and the related mechanisms - Jinhan Yang; Lin Zhang; Tong Wang; Jiajia Zhang; Mingyue Li; Xiaoxia Jin; Xiaoqiong Tan; Gaoyang Wang; Fenghong Zhao; Yaping Jin (Food and Chemical Toxicology, 2023)

Structural annotation, semi-quantification and toxicity prediction of pyrrolizidine alkaloids from functional food: In silico and molecular networking strategy - Yaping Xu; Jie Li; Huajian Mao; Wei You; Jia Chen; Hua Xu; Jianfeng Wu; Ying Gong; Lei Guo; Tao Liu; Wuju Li; Bin Xu; et al. (Food and Chemical Toxicology, 2023)

Barbican-inspired bimetallic core–shell nanoparticles for fabricating natural leather-based radiation protective materials with enhanced X-ray shielding capability - Hao Li; Jibo Zhou; Linping Yan; Rui Zhong; Yaping Wang; Xuepin Liao; Bi Shi (Chemical Engineering Journal, 2023)

Coordination number engineering of Zn single-atom sites for enhanced transfer hydrogenation performance - Yaping Song; Rou Guo; Binbin Feng; Yanghe Fu; Fumin Zhang; Yifei Zhang; De-Li Chen; Jiangwei Zhang; Weidong Zhu (Chemical Engineering Journal, 2023)

Identification of nsLTP family in Chinese white pear (Pyrus bretschneideri) reveals its potential roles in russet skin formation - Jiawei Li; Qi Wang; Yajing Wang; Xinyi Wu; Yaping Liu; Minchen Wan; Lindu Wang; Xiexuan Wang; Cheng Zhang; Xueqian Wang; Xiaomei Tang; Wei Heng (Planta, 2023)

Independent and combined effects of exposure to organophosphate esters on thyroid hormones in children and adolescents - Liqin Hu; Bin Zhou; Yaping Li; Lulu Song; Jin Wang; Meng Yu; Xiang Li; Ling Liu; Jing Kou; Youjie Wang; Xijiang Hu; Surong Mei (Environmental Geochemistry and Health, 2023)

Long-term manuring enhances soil gross nitrogen mineralization and ammonium immobilization in subtropical area - Jun Wang; Lei Wu; Qiong Xiao; Yaping Huang; Kailou Liu; Yan Wu; Dongchu Li; Yinghua Duan; Wenju Zhang (Agriculture, Ecosystems & Environment, 2023)

The association between organophosphate esters exposure and body mass index in children and adolescents: The mediating effect of sex hormones - Yaping Li; Liqin Hu; Bin Zhou; Zhiyi Zheng; Qitong Xu; Jun Liu; Lulu Song; Youjie Wang; Surong Mei (Chemosphere, 2023)

USP18 promotes endometrial receptivity via the JAK/STAT1 and the ISGylation pathway - Xinyan Zhang; Suhua Gong; Haijing Li; Jiaqi Jiang; Yanni Jia; Ruixue Zhang; Haokun Liu; Aihua Wang; Yaping Jin; Pengfei Lin (Theriogenology, 2023)

Elevated CO2 and temperature increase arbuscular mycorrhizal fungal diversity, but decrease root colonization, in maize and wheat - Zihao Liu; Zhenhua Yu; Bin Song; Yansheng Li; Jie Fang; Yaping Guo; Jian Jin; Jonathan M. Adams (Science of The Total Environment, 2023)

A molecular networking-based isolation of gardneria alkaloids from Gardneria distincta and their anti-inflammatory activity - Sifan Teng; Junjie He; Xiaoqian Wang; Yiqian Li; Afsar Khan; Tianrui Zhao; Yudan Wang; Guiguang Cheng; Yaping Liu (Phytochemistry, 2023)

The nitrogen footprint and reactive nitrogen reduction potential of cotton production in China - Weibin Huang; Fengqi Wu; Zhenggui Zhang; Yongming Meng; Jian Wang; Qinqin Li; Yingchun Han; Lu Feng; Xiaofei Li; Guoping Wang; Yaping Lei; Zhengyi Fan; et al. (Journal of Cleaner Production, 2023)

Effect of ultra-high pressure pretreatment on the phenolic profiles, antioxidative activity and cytoprotective capacity of different phenolic fractions from Que Zui tea - Yongpeng Wang; Zhengxuan Wang; Qingwang Xue; Li Zhen; Yudan Wang; Jianxin Cao; Yaping Liu; Afsar Khan; Tianrui Zhao; Guiguang Cheng (Food Chemistry, 2023)

Enhanced arsenite removal from water using zirconium-ferrocene MOFs coupled with peroxymonosulfate:oxidation and multi-sites adsorption mechanism - Zongchen Li; Shengjia Ma; Linfeng Sang; Guojuan Qu; Tao Zhang; Bin Xu; Wei Jin; Yaping Zhao (Chemosphere, 2023)

New insights into membrane fouling during direct membrane filtration of municipal wastewater and fouling control with mechanical strategies - Yu Men; Zifu Li; Lixin Zhu; Xuemei Wang; Shikun Cheng; Yaping Lyu (Science of The Total Environment, 2023)

Origin, composition, and accumulation of dissolved organic matter in a hypersaline lake of the Qinghai-Tibet Plateau - Yaoling Zhang; Keli Yang; Hongmei Chen; Yaping Dong; Wu Li (Science of The Total Environment, 2023)

Research on synthesis and property of nano-textured Sc2O3-MgO efficient antibacterial agents - Ying Wang; Yanjing Liu; Xiyue Li; Yuezhou Liu; Fuming Wang; Yaping Huang; Bing Du; Yongfang Qian; Lihua Lv (JBIC Journal of Biological Inorganic Chemistry, 2023)

Prenatal BPA exposure disrupts male reproductive functions by interfering with DNA methylation and GDNF expression in the testes of male offspring rats - Yaping Mao; Dan Li; Qiaoqiao Yang; Xiucong Pei; Zhiwen Duan; Mingyue Ma (Environmental Science and Pollution Research, 2023)

Interferon-τ -induced ISG15-AS regulates endometrial receptivity during early goat pregnancy - Ruixue Zhang; Xinyan Guo; Hanbing Li; Zuhui Li; Suhua Gong; Haijing Li; Yongjie Ma; Haokun Liu; Chuxi Gao; Aihua Wang; Yaping Jin; Pengfei Lin (Theriogenology, 2023)

Urinary concentrations of organophosphate esters in relation to semen quality: A cross-sectional study - Yaping Li; Dan Luo; Xiaoya Zhao; Han Wang; Zhiyi Zheng; Jun Liu; Chong Liu; Hui Wang; Yingjun Chen; Yinzhu Shang; Wenqing Lu; Surong Mei; et al. (Science of The Total Environment, 2023)

A chromosome-level genome assembly reveals that tandem-duplicated CYP706V oxidase genes control oridonin biosynthesis in the shoot apex of Isodon rubescens - Yuwei Sun; Jie Shao; Haili Liu; Hua Wang; Guangyi Wang; Jianhua Li; Yaping Mao; Zhuo Chen; Ke Ma; Lin Xu; Yong Wang (Molecular Plant, 2023)

Formation of organic chloride in the treatment of textile dyeing sludge by Fenton system - Xiaojun Lai; Xun-an Ning; Yang Li; Nuoyi Huang; Yaping Zhang; Chenghai Yang (Journal of Environmental Sciences, 2023)

Climate warming accelerates cotton growth while cultivar shifts extend the growth period - Wanrui Han; Shengli Liu; Yaping Lei; Yongjiang Zhang; Yingchun Han; Guoping Wang; Lu Feng; Xiaofei Li; Yabing Li; Zhanbiao Wang (Field Crops Research, 2023)

Simultaneous recovery of nutrients and water from human urine by a novel thermally activated peroxydisulfate and membrane distillation integrated system - Yaping Lyu; Xiuwei Ao; Shikun Cheng; Nana Liu; Yu Men; Zifu Li (Chemical Engineering Journal, 2023)

TCR repertoire landscape reveals macrophage-mediated clone deletion in endotoxin tolerance - Juanjuan Zhao; Li Jia; YiJing Tao; Xu Zhao; Jing Yang; Yanxin Lu; Yaping Yan; Ling Mao; Lin Hu; Jia Lu; MengMeng Guo; Chao Chen; et al. (Inflammation Research, 2023)
Background Endotoxin tolerance (ET) is a protective mechanism in the process of sepsis, septic shock, and their sequelae including uncontrolled inflammation. Accumulating evidence has shown that peripheral T cells contribute to the induction of ET. However, what and how T-cell development contributes to ET inductions remain unclear. Methods Mice were intraperitoneally injected with LPS at a concentration of 5 mg/kg to establish an LPS tolerance model and were divided into two groups: a group examined 72 h after LPS injection (72-h group) and a group examined 8 days after LPS injection (8-day group). Injection of PBS was used as a control. We performed high-throughput sequencing to analyze the characteristics and changes of CD4 + SP TCR β CDR3 repertoires with respect to V direct to J rearrangement during the ET induction. Moreover, the proportion and proliferation, as well as surface molecules such as CD80 and CD86, of F4/80 + macrophages were analyzed using FCM. Furthermore, ACT assay was designed and administered by the tail vein into murine LPS-induced mouse model to evaluate the role of F4/80 + macrophages on the development of CD4 + SP thymocytes in ET condition. Results We found that the frequency and characteristics of the TCR β chain CDR3 changed obviously under condition of ET, indicating the occurrence of TCR rearrangement and thymocyte diversification. Moreover, the absolute numbers of F4/80 + macrophages, but not other APCs, were increased in thymic medulla at 72-h group, accompanied by the elevated function-related molecules of F4/80 + macrophages. Furthermore, adoptively transferred OVA 332-339 peptide-loaded macrophages into Rag-1 −/− mice induced the clone deletion of OVA-specific CD4 + SP, thereby ameliorating the pathology in lung tissue in LPS challenge. Conclusions These data reveal that the frequency and characteristics of the TCR β chain CDR3 undergo dynamic programming under conditions of LPS tolerance. Furthermore, the peripheral macrophages may be a key factor which carry peripheral antigen to thymic medulla and affect the negative selection of T-cell population, thereby contributing to the formation of ET. These results suggest that the clone selection in thymus in ET may confer protection against microbial sepsis.

Orychophragmus violaceus/cotton relay intercropping with reduced N application maintains or improves crop productivity and soil carbon and nitrogen fractions - Zhenggui Zhang; Jian Wang; Shiwu Xiong; Weibin Huang; Xiaofei Li; Minghua Xin; Yingchun Han; Guoping Wang; Lu Feng; Yaping Lei; Beifang Yang; Yabing Li; et al. (Field Crops Research, 2023)

Conceptual design of long span steel-UHPC composite network arch bridge - Yaping Lai; Yu Li; Maoke Huang; Lijun Zhao; Jiayong Chen; Yi Min Xie (Engineering Structures, 2023)

Single atomic ruthenium in WO3 boosted hydrogen evolution stability at Ampere-level current density in whole pH range - Hai Liu; Guoying Tan; Mengxuan Li; Zhuang Zhang; Marshet Getaye Sendeku; Yaping Li; Yun Kuang; Xiaoming Sun (Chemical Engineering Journal, 2023)

Unlocking low-temperature and anti-SO2 poisoning performance of bimetallic PdV/TiO2 catalyst for chlorobenzene/NO catalytic removal by antimony modification design - Guobo Li; Shipeng Ding; Xueyan Hou; Kai Shen; Shule Zhang; Yaping Zhang (Chemical Engineering Journal, 2023)

Assessment of Fungal Diversity in Minqin County, a Typical Arid Region in Northwestern China - Zhanwu Peng; Shuwei Wei; Yaping Hu; Bao Qi; Chaofeng Yuan; Qi Wang; Yu Li (Current Microbiology, 2023)

Quantitative evaluation of variation and driving factors of the regional water footprint for cotton production in China - Qinqin Li; Weibin Huang; Jian Wang; Zhenggui Zhang; Yabing Li; Yingchun Han; Lu Feng; Xiaofei Li; Beifang Yang; Guoping Wang; Yaping Lei; Shiwu Xiong; et al. (Sustainable Production and Consumption, 2023)

3D natural fracture model of shale reservoir based on petrophysical characterization - Yaping Li; Xiaowei Chen; Yongbo Shao (Journal of Structural Geology, 2023)

Fabrication and characterization of l-ascorbyl palmitate and phospholipid-based hybrid liposomes and their impacts on the stability of loaded hydrophobic polyphenols - Mianhong Chen; Ruyi Li; Xuli Lu; Yaping Dai; Tinghui Chen; Yuhang Xing; Lu Xue; Zhihao Duan; Wei Zhou; Jihua Li (Food Chemistry, 2023)

Expanding the gallery of solvent-free nanofluids: Using layered double hydroxides as core nanostructures - Xiaoqian Ju; Zhiyuan Yang; Dechao Wang; Xinbo Duan; Yangyang Xin; Hanbo Zhu; Xiaoqian Li; Yinyan Li; Dongdong Yao; Yaping Zheng (Chemical Engineering Journal, 2023)

Carbon layer encapsulation strategy for designing multifunctional core-shell nanorod aerogels as high-temperature thermal superinsulators - Fengqi Liu; Chenbo He; Yonggang Jiang; Yaping Yang; Fei Peng; Lanfang Liu; Jing Men; Junzong Feng; Liangjun Li; Guihua Tang; Jian Feng (Chemical Engineering Journal, 2023)

Spatial and temporal characteristics of nighttime UHII based on local climate zone scheme using mobile measurement-A case study of Changsha - Yaping Chen; Jiayu Li; Yinze Hu; Luyun Liu (Building and Environment, 2023)

Parameter identification and state estimation for nuclear reactor operation digital twin - Helin Gong; Tao Zhu; Zhang Chen; Yaping Wan; Qing Li (Annals of Nuclear Energy, 2023)

Higher pH is associated with enhanced co‐occurrence network complexity, stability and nutrient cycling functions in the rice rhizosphere microbiome - Yaping Guo; Bin Song; Anqi Li; Qi Wu; Haili Huang; Na Li; Ying Yang; Jonathan Miles Adams; Lin Yang (Environmental Microbiology, 2022)
The rice rhizosphere microbiota is crucial for crop yields and nutrient use efficiency. However, little is known about how co‐occurrence patterns, keystone taxa and functional gene assemblages relate to soil pH in the rice rhizosphere soils. Using shotgun metagenome analysis, the rice rhizosphere microbiome was investigated across 28 rice fields in east‐central China. At higher pH sites, the taxonomic co‐occurrence network of rhizosphere soils was more complex and compact, as defined by higher average degree, graph density and complexity. Network stability was greatest at medium pH (6.5

A 10-miRNA risk score-based prediction model for pathological complete response to neoadjuvant chemotherapy in hormone receptor-positive breast cancer - Chang Gong; Ziliang Cheng; Yaping Yang; Jun Shen; Yingying Zhu; Li Ling; Wanyi Lin; Zhigang Yu; Zhihua Li; Weige Tan; Chushan Zheng; Wenbo Zheng; et al. (Science China Life Sciences, 2022)

The structure, characterization and dual-activity of exopolysaccharide produced by Bacillus enclensis AP-4 from deep-sea sediments - Xin Hu; Fengshu Li; Xiuli Zhang; Yaping Pan; Jinren Lu; Yiming Li; Mutai Bao (Frontiers in Marine Science, 2022)
In recent years, the exopolysaccharide (EPS) produced by deep-sea bacteria has attracted the interest of various researchers. In the present study, we have explored the properties and structure of a novel exopolysaccharide (called BPS) produced by Bacillus enclensis AP-4 from deep-sea sediments. The maximum yield of BPS was 4.23 ± 0.17 g L −1 in a 2216E modified medium. 1 H NMR studies of the purified BPS displayed α and β-configuration sugar residues, including mannose, glucosamine, glucose, galactose, and xylose in a molar ratio of 1.00: 0.09: 0.04: 0.09: 0.07. BPS showed a molecular weight of 23,434 Da and was abundant in hydroxyl and amino residues. In addition, BPS exhibited a rod-like structure with a rough surface and was dominated by C, N, and O elements. The exopolysaccharide demonstrated remarkable thermal stability, high degradation temperature, and excellent emulsification capacity compared to most reported exopolysaccharides. Moreover, BPS displayed better quenching activities against the four radicals, which provided favorable protection for the strain. Finally, the freezing experiment investigated the cryoprotective effect of BPS on E. coli and S. aureus . BPS effectively improved the cell survival ratio and maintained the activity of Na + /K + -ATPase, which facilitates culture preservation. To the best of our knowledge, our work is the first report suggesting that marine exopolysaccharide has dual-activity. This work presents the foundation for the analysis of the structure and properties of exopolysaccharides produced by deep-sea bacteria.

Induced mutation in ELONGATED HYPOCOTYL5 abolishes anthocyanin accumulation in the hypocotyl of pepper - Rong Chen; Can Yang; Hu Gao; Chunmei Shi; Zhiying Zhang; Guangyu Lu; Xinyan Shen; Yaping Tang; Feng Li; Yongen Lu; Bo Ouyang (Theoretical and Applied Genetics, 2022)

Development of center pivot irrigation farmlands from 2009 to 2018 in the Mu Us dune field, China: Implication for land use planning - Xiaokang Liu; Zhibao Dong; Yaping Ding; Ruijie Lu; Liyun Liu; Zhiyong Ding; Yijing Li (Journal of Geographical Sciences, 2022)

Gene expression in the microbial consortia of colonial Microcystis aeruginosa ‐a potential buoyant particulate biofilm - Limei Shi; Yuanfeng Cai; Shengling Gao; Daoyan Fang; Yaping Lu; Pengfu Li; Qinglong L. Wu (Environmental Microbiology, 2022)
Microcystis spp., notorious bloom‐forming cyanobacteria, are often present in colony form in eutrophic lakes worldwide. Uncovering the mechanisms underlying Microcystis colony formation and maintenance is vital to controlling the blooms, but it has long been a challenge. Here, bacterial communities and gene expression patterns of colonial and unicellular forms of one non‐axenic strain of Microcystis aeruginosa isolated from Lake Taihu were compared. Evidently, different microbial communities between them were observed through 16S rDNA MiSeq sequencing. Metatranscriptome analyses revealed that transcripts for pathways involved in bacterial biofilm formation, such as biosynthesis of peptidoglycan and arginine by Bacteroidetes , methionine biosynthesis, alginate metabolism, flagellum, and motility, as well as widespread colonization islands by Proteobacteria , were highly enriched in the colonial form. Furthermore, transcripts for nitrogen fixation and denitrification pathways by Proteobacteria that usually occur in biofilms were significantly enriched in the colonial Microcystis . Results revealed that microbes associated with Microcystis colonies play important roles through regulation of biofilm‐related genes in colony formation and maintenance. Moreover, Microcystis colony represents a potential ‘buoyant particulate biofilm’, which is a good model for biofilm studies. The biofilm features of colonial Microcystis throw a new light on management and control of the ubiquitous blooms in eutrophic waters.

A New Dual-peak Fluorescent Probe for Water Content Detection Made From Taxus - Gang Wang; Yaping Li; Haipeng Chen; Shuqin Tang; Yiyang Cheng; Yuhong Yu; Abdul Qayoom Majeedano; Shangrao Pu; Gang Wang (Journal of Fluorescence, 2022)

A FRET Fluorescent Sensor for Ratiometric and Visual Detection of Sulfide Based on Carbon Dots and Silver Nanoclusters - Jing Yang; Yan Huang; Hanyue Cui; Li Li; Yaping Ding (Journal of Fluorescence, 2022)

Metagenomics-based antibiotic resistance genes diversity and prevalence risk revealed by pathogenic bacterial host in Taihu Lake, China - Ying Bai; Xiaohong Ruan; Rongfu Li; Yaping Zhang; Zongzhi Wang (Environmental Geochemistry and Health, 2022)

Regulation of wound healing and fibrosis by galectins - Dong Yu; Ming Bu; Ping Yu; Yaping Li; Yang Chong (Journal of Molecular Medicine, 2022)

Organophosphate esters in children and adolescents in Liuzhou city, China: concentrations, exposure assessment, and predictors - Meng Yu; Xiang Li; Bingqing Liu; Yaping Li; Ling Liu; Limei Wang; Lulu Song; Youjie Wang; Liqin Hu; Surong Mei (Environmental Science and Pollution Research, 2022)

The behavior of REEs indicates the dolomite petrogenesis and a unique dolomitization model of the Middle Permian Qixia formation in Northwest Sichuan Basin, China - Shengyang Xie; Xingzhi Wang; Bo Li; Long Wen; Liang Xu; Yao Du; Lin Xie; Yong Li; Yaping Wang; Yawen Li (Carbonates and Evaporites, 2022)

A Significant Fluorescent Aptamer Sensor Based on Carbon Dots and Graphene Oxide for Highly Selective Detection of Progesterone - Hanyue Cui; Huan Lu; Jing Yang; Yao Fu; Yan Huang; Li Li; Yaping Ding (Journal of Fluorescence, 2022)

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Soil phosphorus availability and stoichiometry determine microbial activity and functional diversity of fluvo-aquic soils under long-term fertilization regimes - Wei He; Wenhua Ye; Mingjie Sun; Yaping Li; Manman Chen; Meng Wei; Guoqing Hu; Quangang Yang; Hong Pan; Yanhong Lou; Hui Wang; Yuping Zhuge (Journal of Soils and Sediments, 2022)

Biological monitoring and health assessment of 21 metal(loid)s in children and adolescents in Liuzhou City, Southwest China - Yaping Li; Yu Zhang; Meng Yu; Liqin Hu; Ting Zeng; Ling Liu; Limei Wang; Liangqiong Deng; Xiang Li; Ping Liu; Dingyuan Zeng; Surong Mei (Environmental Science and Pollution Research, 2022)

A 90-Day Subchronic Toxicity Study of Consumption of GH-Transgenic Triploid Carp in Wistar Rats - Jingya Guo; Yongming Li; Yaping Wang; Boyong Chen; Yingxin Hu; Yasheng Musha; Xiaoyun He; Tao Tong; Kunlun Huang (Fishes, 2022)
Genetic modification (GM) offers an alternative strategy to conventional animal breeding. The present study was carried out to investigate the potential health effects of the consumption of growth hormone-transgenic triploid carp (GH-ttc) through a 90-day subchronic rodent feeding study. Wistar rats (n = 10/sex/group) were given formulated diets containing GH-ttc or non-GM carp at an incorporated rate of 2.5%, 5%, or 10% (w/w) for 90 days. An additional control group of rats (n = 10/sex/group) was fed a basic rodent diet. During the 90-day study, clinical observation, ophthalmic examination, body weight, and food intake were evaluated. At the end of the study, rats were killed, and the hematology, serum chemistry, urine test, necropsy, and histopathology were assessed. Compared with the non-GM carp and the basic control groups, no biologically significant differences were observed on clinical signs of toxicity, body weights, food intake, hematology, serum chemistry, urinalysis, organ weight, and histopathology on selected organs for the GH-ttc group. The results of this 90-day subchronic feeding study indicated that, at the dose level used in this study, consumption of GH-ttc showed no subchronic toxicity to Wistar rats.

Chemical composition and Pb(II) binding of dissolved organic matter in a hypersaline lake in China - Keli Yang; Yaoling Zhang; Yaping Dong; Wu Li (Journal of Oceanology and Limnology, 2022)

Longitudinal residual circulation in the South Passage of Yangtze Estuary: Combined influences from runoff, tide and bathymetry - Lifen Zhang; Zuosheng Yang; Fan Zhang; Zhanhai Li; Yaping Wang; Shu Gao (Science China Earth Sciences, 2021)

Tracking historical storm records from high-barrier lagoon deposits on the southeastern coast of Hainan Island, China - Liang Zhou; Xiaomei Xu; Yaping Wang; Jianjun Jia; Yang Yang; Gaocong Li; Changliang Tong; Shu Gao (Acta Oceanologica Sinica, 2021)

ADV-Based Investigation on Bed Level Changes Over a Meso-Macro Tidal Beach - Wenhong Pang; Xiaoyan Zhou; Zhijun Dai; Shushi Li; Hu Huang; Yaping Lei (Frontiers in Marine Science, 2021)
Beach intra-tidal bed level changes are of significance to coastal protection amid global climate changes. However, due to the limitation of instruments and the disturbance induced by wave motions superimposed on water levels, it was difficult to detect the high-frequency oscillation of the submerged beach bed level. In this study, an observation, lasting for 12 days and covering the middle tide to the following spring tide, was conducted on a meso-macro tidal beach, Yintan Beach, to simultaneously detect the characteristics and influence mechanism of bed level changes at intra-tidal and tidal cycle scales. The collected data included water depth, suspended sediment concentration (SSC), waves, high-frequency three-dimensional (3-D) velocity, and the distance of the seabed to the acoustic Doppler velocimeter (ADV) probe, which were measured by an optical backscatter sensor, two Tide & Wave Recorder-2050s, and an ADV, respectively. The results showed that the tidal cycle-averaged bed level decreased by 58.8 mm, increased by 12.6 mm, and increased by 28.9 mm during neap, middle, and spring tides in succession, respectively, compared with the preceding tidal regimes. The net erosion mainly resulted from large incident wave heights and the consequent strong offshore-directed sediment transport induced by undertows. Moreover, the variations in the bed level were more prominent during a neap to middle tides than during middle to spring tides, which were jointly caused by the wave-breaking probability regulated by water depth and the relative residence times of shoaling wave, breaker, and surf zones that were determined by relative tidal range. In terms of the intra-tidal bed level, it displayed an intra-tidal tendency of increase during floods and decrease during ebb tides, i.e., the intra-tidal bed level changes were controlled by water depth, which modulated the effects of waves on sediment resuspension and vertical sediment exchange. To be specific, waves and SSC were responsible for the intra-tidal bed level changes under low-energy wave conditions, while mean current and bedform exerted important influences on the variations of the intra-tidal bed level under moderate wave conditions, which broke the foregoing interrelation between bed level, waves, and SSC. This study, therefore, emphasizes the usage of ADV measurement to investigate bed level changes in sandy coasts.

Conversion of organics and minerals into electricity and microalgae using a dual-membrane cylinder photo-microbial fuel cell - Gang Li; Haixing Chang; Yajun Zou; Jianzhi Yue; Yaping Zheng; Haowen Feng; Haihua Wu; Wenbo Wu; Jie Lou; Xueqiang Qi; Xingran Zhang (Environmental Chemistry Letters, 2021)

Pituitary Adenylate Cyclase-Activating Polypeptide Protects Against Cognitive Impairment Caused by Chronic Cerebral Hypoperfusion - Xiaosu Guo; Ye Tian; Yaping Yang; Shiping Li; Li Guo; Jiong Shi (Molecular Neurobiology, 2021)

Facile carboxylation of natural eggshell membrane for highly selective uranium (VI) adsorption from radioactive wastewater - Sensen Xuan; Bo Zhang; Lin Xiao; Guoqiang Li; Yaping Zhang; Yabin Zhang; Jinchao Li (Environmental Science and Pollution Research, 2021)

Physiological and transcriptomic responses of Mikania micrantha stem to shading yield novel insights into its invasiveness - Zhaoyang Jiang; Yutao Wang; Yaping Zheng; Minling Cai; Changlian Peng; Weihua Li (Biological Invasions, 2021)

The emerging role of circular RNAs in cardiovascular diseases - Yuejia Ding; Chunmiao Lu; Wanqin Zhang; Yuan Wang; Yanyang Li; Yaping Zhu; Shichao Lv; Junping Zhang (Journal of Physiology and Biochemistry, 2021)

Exosomes derived from astrocytes after oxygen-glucose deprivation promote differentiation and migration of oligodendrocyte precursor cells in vitro - Yaping Xu; Yeye Tian; Yao Wang; Li Xu; Guini Song; Qiao Wu; Wei Wang; Minjie Xie (Molecular Biology Reports, 2021)

The influence of VDR polymorphisms on the type 2 diabetes susceptibility in Chinese: an interaction with hypertriglyceridemia - Dongdong Zhang; Cheng Cheng; Yan Wang; Yuan Xue; Yaping Liu; Yiming Liu; Mingming Feng; Ze Xu; Wenjie Li; Xing Li (Molecular Genetics and Genomics, 2021)

Effects of Exogenous Application of GA4+7 and NAA on Sugar Accumulation and Related Gene Expression in Peach Fruits During Developing and Ripening Stages - Xiongwei Li; Pan Liu; Jingyi Zhou; Mingshen Su; Yaping Ma; Huijuan Jia; Jihong Du; Zhongshan Gao; Zhengwen Ye (Journal of Plant Growth Regulation, 2021)

Effects of UV-modified biochar derived from phytoremediation residue on Cd bioavailability and uptake in Coriandrum sativum L. in a Cd-contaminated soil - Yaping Zhang; Zhenyan Chen; Chunhong Chen; Fangzhou Li; Kai Shen (Environmental Science and Pollution Research, 2021)

Predicting sediment flux from continental shelf islands, southeastern China - Gaocong Li; Xiaoming Xia; Jianjun Jia; Yaping Wang; Tinglu Cai; Shu Gao (Journal of Oceanology and Limnology, 2021)

Geometric modeling of Holocene large-river delta growth patterns, as constrained by environmental settings - Gaocong Li; Qiong Xia; Yaping Wang; Zhiqiang Li; Shu Gao (Science China Earth Sciences, 2021)

Docetaxel-loaded D-α-tocopheryl polyethylene glycol-1000 succinate liposomes improve lung cancer chemotherapy and reverse multidrug resistance - Na Li; Yaping Mai; Qiang Liu; Guojing Gou; Jianhong Yang (Drug Delivery and Translational Research, 2021)

Transcriptomic analysis reveals somatic embryogenesis-associated signaling pathways and gene expression regulation in maize (Zea mays L.) - Meiqi Ding; Haixiao Dong; Yingjie Xue; Shengzhong Su; Ying Wu; Shipeng Li; Hongkui Liu; He Li; Junyou Han; Xiaohui Shan; Yaping Yuan (Plant Molecular Biology, 2020)

The Beneficial Effects of Aluminum on the Plant Growth in Camellia japonica - Yuanjiao Liu; Jingyu Tao; Jing Cao; Yaping Zeng; Xi Li; Jun Ma; Zhuo Huang; Mingyan Jiang; Lingxia Sun (Journal of Soil Science and Plant Nutrition, 2020)

A Fluorescent “Turn-off” Probe for the Determination of Curcumin Using Upconvert Luminescent Carbon Dots - Chenhong Yu; Qi Zhuang; Hanyue Cui; Li Li; Yaping Ding; Jiaxin Lin; Yingchun Duan (Journal of Fluorescence, 2020)

Sediment transport under increasing anthropogenic stress: Regime shifts within the Yellow River, China - Shuang Song; Shuai Wang; Bojie Fu; Yanxu Liu; Kevin Wang; Yikai Li; Yaping Wang (Ambio, 2020)

Study of the geostatistical grid maths operation method of quantifying water movement in soil layers of a cotton field * - Liyuan Liu; Fangfang Xing; Yabing Li; Yingchun Han; Zhanbiao Wang; Xiaoyu Zhi; Guoping Wang; Lu Feng; Beifang Yang; Yaping Lei; Zhengyi Fan; Wenli Du (Irrigation and Drainage, 2020)
The precise quantification of water movement in different field soil layers is important for variable‐rate irrigation and fertilization. To this end, a field experiment based on a geostatistical approach was conducted in southern Anyang, Henan, China, to examine soil water movement in a cotton field with drip irrigation by measuring the soil water content (SWC) data on a regular 100 × 80 cm grid. The result shows that the temporal and spatial variation of soil moisture decreased with the increase of soil depth at different points, and apparent spatial heterogeneity was observed under different soil conditions through a semivariogram analysis. The variation of soil moisture at different soil profiles was affected by the cotton plants and drip lines in non‐irrigation and irrigation periods respectively. The level of the change at 20 cm was more than 70 cm in the horizontal direction in the two periods, however the degree of change at 40 cm in the irrigation period was more than 70 cm in the vertical direction, while contrary results were shown in the non‐irrigation period. Moreover, the results indicated that the trapezoidal rule could be applied to quantify the volume of water movement precisely.

Could urinary ACE2 protein level help identify individuals susceptible to SARS-CoV-2 infection and complication? - Xiaotian Ni; Changqing Sun; Yaping Tian; Yanjie Huang; Tongqing Gong; Lan Song; Xing Yang; Kai Li; Nairen Zheng; Jianping Wang; Hongxing Wu; Ruoxian Zhang; et al. (Science China Life Sciences, 2020)

Simulation of oyster ecological carrying capacity in Sanggou Bay in the ecosystem context - Yaping Gao; Jianguang Fang; Fan Lin; Fengxue Li; Wenhao Li; Xiaoqin Wang; Meirong Du; Jinghui Fang; Weiwei Jiang; Hui Liu; Yitao Zhang; Junwei Wang; et al. (Aquaculture International, 2020)

Introduction of a multicenter online database for non-metastatic breast cancer in China - Yaping Yang; Jieqiong Liu; Min Peng; Fengxi Su; Xiaoming Xie; Zhenzhen Liu; Jundong Wu; Wei Wei; Dongxian Zhou; Weiwen Li; Ailing Zhang; Guosen Su; et al. (Science China Life Sciences, 2020)

De novo transcriptome of the whole-body of the gastropod mollusk Philomycus bilineatus, a pest with medical potential in China - Zhongjie Li; Yaping Yuan; Miaomiao Meng; Ping Hu; Yong Wang (Journal of Applied Genetics, 2020)

Improved activity of Ho-modified Mn/Ti catalysts for the selective catalytic reduction of NO with NH3 - Yaping Zhang; Peng Wu; Guobo Li; Ke Zhuang; Kai Shen; Sheng Wang; Tianjiao Huang (Environmental Science and Pollution Research, 2020)

A microcosm study on persulfate oxidation combined with enhanced bioremediation to remove dissolved BTEX in gasoline-contaminated groundwater - Yuan Xia; Yaping Cheng; Liuyue Li; Yudao Chen; Yaping Jiang (Biodegradation, 2020)

Leaching Behaviour and Enhanced Phytoextraction of Additives for Cadmium-Contaminated Soil by Pennisetum sp. - Fangzhou Li; Yaping Zhang; Shefeng Hao; Weiwei Xu; Kai Shen; Zhen Long (Bulletin of Environmental Contamination and Toxicology, 2020)

Interactive effects of exogenous melatonin and Rhizophagus intraradices on saline-alkaline stress tolerance in Leymus chinensis - Yurong Yang; Yaping Cao; Zhenxin Li; Anastasiia Zhukova; Songtao Yang; Jinlong Wang; Zhanhui Tang; Yonghong Cao; Yifei Zhang; Deli Wang (Mycorrhiza, 2020)

Ameliorative effect of naringin against thiram-induced tibial dyschondroplasia in broiler chicken - Xiong Jiang; Aoyun Li; Yaping Wang; Mudassar Iqbal; Muhammad Waqas; Hao Yang; Zhixing Li; Khalid Mehmood; Hammad Qamar; Jiakui Li (Environmental Science and Pollution Research, 2020)

Characterization of longshore currents in southern East China Sea during summer and autumn - Peng Li; Benwei Shi; Yangang Li; Sijian Wang; Xin Lv; Yaping Wang; Qing Tian (Acta Oceanologica Sinica, 2020)

Identification and expression analysis of microRNAs in tibial growth plate of chicken through thiram toxicity - Zhixing Li; Aoyun Li; Jialu Zhang; Yaping Wang; Hui Zhang; Khalid Mehmood; Yi Lian; Mudassar Iqbal; Jiakui Li (Environmental Science and Pollution Research, 2020)

Simulation of Yesso scallop, Patinopecten yessoensis, growth with a dynamic energy budget (DEB) model in the mariculture area of Zhangzidao Island - Weiwei Jiang; Fan Lin; Meirong Du; Jianguang Fang; Jinghui Fang; Yaping Gao; Xiaoqin Wang; Fengxue Li; Shipeng Dong; Xing Hou; Zengjie Jiang (Aquaculture International, 2020)

Porphyromonas gingivalis degrades integrin β1 and induces AIF-mediated apoptosis of epithelial cells - Qian Li; Jie Zhou; Li Lin; Haijiao Zhao; Lei Miao; Yaping Pan (Infectious Diseases, 2019)

Application of next-generation sequencing to screen for pathogenic mutations in 123 unrelated Chinese patients with Marfan syndrome or a related disease - Jiacheng Li; Chaoxia Lu; Wei Wu; Yaping Liu; Rongrong Wang; Nuo Si; Xiaolu Meng; Shuyang Zhang; Xue Zhang (Science China Life Sciences, 2019)

Review of Chinese atmospheric science research over the past 70 years: Synoptic meteorology - Zhiyong Meng; Fuqing Zhang; Dehai Luo; Zhemin Tan; Juan Fang; Jianhua Sun; Xueshun Shen; Yunji Zhang; Shuguang Wang; Wei Han; Kun Zhao; Lei Zhu; et al. (Science China Earth Sciences, 2019)

Origin of crystal dolomite and its reservoir formation mechanism in the Xixiangchi Formation, Upper Cambrian in Southeastern Sichuan basin - Xuefei Yang; Zisang Huang; Xingzhi Wang; Yaping Wang; Ke Li; Deming Zeng (Carbonates and Evaporites, 2019)

Cloud type identification for a landfalling typhoon based on millimeter-wave radar range-height-indicator data - Zhoujie Cheng; Ming Wei; Yaping Zhu; Jie Bai; Xiaoguang Sun; Li Gao (Frontiers of Earth Science, 2019)

Neural Stem Cells Transfected with Leukemia Inhibitory Factor Promote Neuroprotection in a Rat Model of Cerebral Ischemia - Lili Tian; Wenli Zhu; Yuanchu Liu; Ye Gong; Aowei Lv; Zhen Wang; Xiaoli Ding; Shaowu Li; Ying Fu; Yi Lin; Yaping Yan (Neuroscience Bulletin, 2019)

Erratum to: Rapid generation of genetic diversity by multiplex CRISPR/Cas9 genome editing in rice - Lan Shen; Yufeng Hua; Yaping Fu; Jian Li; Qing Liu; Xiaozhen Jiao; Gaowei Xin; Junjie Wang; Xingchun Wang; Changjie Yan; Kejian Wang (Science China Life Sciences, 2019)

Enhanced Phytoextraction for Co-contaminated Soil with Cd and Pb by Ryegrass (Lolium perenne L.) - Yaping Zhang; Fangzhou Li; Weiwei Xu; Jinghua Ren; Sihui Chen; Kai Shen; Zhen Long (Bulletin of Environmental Contamination and Toxicology, 2019)

Protective effect of Astragaloside IV to inhibit thiram-induced tibial dyschondroplasia - Khalid Mehmood; Hui Zhang; Wangyuan Yao; Xiong Jiang; Muhammad Waqas; Aoyun Li; Yaping Wang; Li Lei; Lihong Zhang; Hammad Qamar; Jiakui Li (Environmental Science and Pollution Research, 2019)

Immunity induced by recombinant attenuated IHNV (infectious hematopoietic necrosis virus)‐G N438A expresses VP2 gene‐encoded IPNV (infectious pancreatic necrosis virus) against both pathogens in rainbow trout - Yaping Chen; Mengting Guo; Yanxue Wang; Xiaojing Hua; Shuai Gao; Yuting Wang; Dechuan Li; Wen Shi; Lijie Tang; Yijing Li; Min Liu (Journal of Fish Diseases, 2019)
Infectious hematopoietic necrosis virus (IHNV) and infectious pancreatic necrosis virus (IPNV) are important pathogens in rainbow trout farming worldwide. Their co‐infection is also common, which causes great economic loss in juvenile salmon species. Development of a universal virus vaccine providing broadly cross‐protective immunity will be of great importance. In this study, we generated two recombinant (r) virus (rIHNV‐N438A‐ΔNV‐EGFP and rIHNV‐N438A‐ΔNV‐VP2) replacing the NV gene of the backbone of rIHNV at the single point mutation at residue 438 with an efficient green fluorescent protein ( EGFP ) reporter gene and antigenic VP2 gene of IPNV. Meanwhile, we tested their efficacy against the wild‐type (wt) IHNV HLJ‐09 virus and IPNV serotype Sp virus challenge. The relative per cent survival rates of two recombinant viruses against (wt) IHNV HLJ‐09 virus challenge were 84.6% and 81.5%, respectively. Simultaneously, the relative per cent survival rate of rIHNV‐N438A‐ΔNV‐VP2 against IPNV serotype Sp virus challenge was 88.9%. It showed the two recombinant viruses had high protection rates and induced a high level of antibodies against IHNV or IPNV. Taken together, these results suggest the VP2 gene of IPNV can act as candidate gene for vaccine and attenuated multivalent live vaccines and molecular marker vaccines have potential application for viral vaccine.

Comparative genomics for non-O1/O139 Vibrio cholerae isolates recovered from the Yangtze River Estuary versus V. cholerae representative isolates from serogroup O1 - Li Gong; Pan Yu; Huajun Zheng; Wenyi Gu; Wei He; Yadong Tang; Yaping Wang; Yue Dong; Xu Peng; Qunxin She; Lu Xie; Lanming Chen (Molecular Genetics and Genomics, 2019)

The Resveratrol Alleviates the Hepatic Toxicity of CuSO4 in the Rat - Yaping Tian; Bing Wu; Xiaoping Li; Xuefei Jin; Fuqiang Zhang; Chunyan Jiang; Wenzhou Xu; Hang Li; Heyuan Wang (Biological Trace Element Research, 2019)

Deep sequencing of small RNAs from 11 tissues of grass carp Ctenopharyngodon idella and discovery of sex‐related microRNAs - Liangming Chen; Rong Huang; Denghui Zhu; Cheng Yang; Libo He; Yongming Li; Lanjie Liao; Zuoyan Zhu; Yaping Wang (Journal of Fish Biology, 2019)
This research identified 169 known microRNAs (miRNAs), 380 novel miRNAs, and 30,538 targets in 11 tissues (blood, brain, derma, gill, heart, intestine, kidney, liver, muscle, pronephros, and spleen) from grass carp Ctenopharyngodon idella with high‐throughput sequencing (HTS). Transcripts per million (TPM) expression analysis detected 41 brain‐enriched miRNAs (accounting for 61.19% of all tissue‐enriched miRNAs). Real‐time quantitative PCR (RT‐qPCR) confirmed that 21 of 24 randomly selected tissue‐enriched miRNAs from the TPM analysis were indeed tissue‐enriched ( P dmrt ) involved in sex differentiation. RT‐qPCR revealed that cid‐miR ‐138 was more highly expressed in testis than in ovary ( P dmrt4a ( P cid‐miR ‐138– dmrt4a in neuroendocrine mechanisms related to brain‐pituitary networks during sex development. The discovery of miRNAs from 11 C. idella tissues expands the available fish mi R NA database, and enhances our understanding of the role of sex‐related miRNAs in tissue differentiation and maintenance of specific tissue functions in fishes.

Population genetic patterns of the solitary tunicate, Molgula manhattensis, in invaded Chinese coasts: large-scale homogeneity but fine-scale heterogeneity - Yiyong Chen; Shiguo Li; Yaping Lin; Hongjun Li; Aibin Zhan (Marine Biodiversity, 2018)

Correlation of IL-31 gene polymorphisms with susceptibility and clinical recurrence of bladder cancer - Qin Li; Tielong Tang; Peng Zhang; Chenlu Liu; Yan Pu; Yan Zhang; Huizi Song; Yanyun Wang; Yaping Song; Min Su; Bin Zhou; Lin Zhang (Familial Cancer, 2018)

Study on the Combined Application of CFAR and Deep Learning in Ship Detection - Ruifu Wang; Jie Li; Yaping Duan; Hongjun Cao; Yingjie Zhao (Journal of the Indian Society of Remote Sensing, 2018)

Selection of growth-related genes and dominant genotypes in transgenic Yellow River carp Cyprinus carpio L. - Lifei Luo; Rong Huang; Aidi Zhang; Cheng Yang; Liangming Chen; Denghui Zhu; Yongming Li; Libo He; Lanjie Liao; Zuoyan Zhu; Yaping Wang (Functional & Integrative Genomics, 2018)

LncRNA Gm2044 highly expresses in spermatocyte and inhibits Utf1 translation by interacting with Utf1 mRNA - Ke Hu; Leina Li; Yaping Liao; Meng Liang (Genes & Genomics, 2018)

Spatial and temporal precipitation patterns characterized by TRMM TMPA over the Qinghai-Tibetan plateau and surroundings - Ziqiang Ma; Yaping Xu; Jie Peng; Qiuxiao Chen; Dan Wan; Kang He; Zhou Shi; Hongyi Li (International Journal of Remote Sensing, 2018)

Sediment flux from the Zhoushan Archipelago, eastern China - Gaocong Li; Shu Gao; Yaping Wang; Chunyan Li (Journal of Geographical Sciences, 2018)

Controlled Release of the Nimodipine-Loaded Self-Microemulsion Osmotic Pump Capsules: Development and Characterization - Yaping Huang; Sisi Zhang; Huifen Shen; Jinqing Li; Chongkai Gao (AAPS PharmSciTech, 2018)

Chemical characterization of fractions of dissolved humic substances from a marginal sea—a case from the Southern Yellow Sea - Yaoling Zhang; Keli Yang; Jinzhou Du; Fenfen Zhang; Yaping Dong; Wu Li (Journal of Oceanology and Limnology, 2018)

A novel homozygous complex deletion in CFTR caused cystic fibrosis in a Chinese patient - Keqiang Liu; Yaping Liu; Xue Li; Kai-Feng Xu; Xinlun Tian; Xue Zhang (Molecular Genetics and Genomics, 2017)

Size fraction of phytoplankton and the contribution of natural plankton to the carbon source of Zhikong scallop Chlamys farreri in mariculture ecosystem of the Sanggou Bay - Zengjie Jiang; Meirong Du; Jinghui Fang; Yaping Gao; Jiaqi Li; Li Zhao; Jianguang Fang (Acta Oceanologica Sinica, 2017)

Temporal and spatial variations of aquatic environmental characteristics and sediment bacterial community in five regions of Lake Taihu - Yu Wan; Yang Bai; Jia He; Yaping Zhang; Rongfu Li; Xiaohong Ruan (Aquatic Ecology, 2017)

LINGO-1-Fc-Transduced Neural Stem Cells Are Effective Therapy for Chronic Stage Experimental Autoimmune Encephalomyelitis - Xing Li; Yuan Zhang; Yaping Yan; Bogoljub Ciric; Cun-Gen Ma; Jeannie Chin; Mark Curtis; Abdolmohamad Rostami; Guang-Xian Zhang (Molecular Neurobiology, 2017)

Rapid generation of genetic diversity by multiplex CRISPR/Cas9 genome editing in rice - Lan Shen; Yufeng Hua; Yaping Fu; Jian Li; Qing Liu; Xiaozhen Jiao; Gaowei Xin; Junjie Wang; Xingchun Wang; Changjie Yan; Kejian Wang (Science China Life Sciences, 2017)

IL-5 blocks apoptosis and tau hyperphosphorylation induced by Aβ25–35 peptide in PC12 cells - Yuanyuan Zhou; Chaoyan Li; Deheng Li; Yaping Zheng; Jin Wang (Journal of Physiology and Biochemistry, 2017)

Classifying the sedimentary environments of the Xincun Lagoon, Hainan Island, by system cluster and principal component analyses - Yang Yang; Shu Gao; Liang Zhou; Yunwei Wang; Gaocong Li; Yaping Wang; Zhuochen Han; Peihong Jia (Acta Oceanologica Sinica, 2017)

Analysis of the characteristics of offshore currents in the Changjiang (Yangtze River) estuarine waters based on buoy observations - Peng Li; Benwei Shi; Yaping Wang; Weihua Qin; Yangang Li; Jian Chen (Acta Oceanologica Sinica, 2017)

Autoantibody to MOG suggests two distinct clinical subtypes of NMOSD - Yaping Yan; Yujing Li; Ying Fu; Li Yang; Lei Su; Kaibin Shi; Minshu Li; Qiang Liu; Aimee Borazanci; Yaou Liu; Yong He; Jeffrey L. Bennett; et al. (Science China Life Sciences, 2016)

Alterations of Synaptic Proteins in the Hippocampus of Mouse Offspring Induced by Developmental Lead Exposure - Haiyang Yu; Yingjun Liao; Tingting Li; Yan Cui; Gaoyang Wang; Fenghong Zhao; Yaping Jin (Molecular Neurobiology, 2016)

Environmental filtering decreases with fish development for the assembly of gut microbiota - Qingyun Yan; Jinjin Li; Yuhe Yu; Jianjun Wang; Zhili He; Joy D. Van Nostrand; Megan L. Kempher; Liyou Wu; Yaping Wang; Lanjie Liao; Xinghao Li; Shu Wu; et al. (Environmental Microbiology, 2016)
Summary Gut microbiota typically occupy habitats with definable limits/borders that are comparable to oceanic islands. The gut therefore can be regarded as an ‘island’ for the assembly of microbial communities within the ‘sea’ of surrounding environments. This study aims to reveal the ecological mechanisms that govern microbiota in the fish gut ‘island’ ecosystem. Taxonomic compositions, phylogenetic diversity, and community turnover across host development were analyzed via the high‐throughput sequencing of 16S rRNA gene amplicons. The results indicate that the Shannon diversity of gut microbiota in the three examined freshwater fish species all significantly decreased with host development, and the dominant bacterial taxa also changed significantly during host development. Null model and phylogenetic‐based mean nearest taxon distance (MNTD) analyses suggest that host gut environmental filtering led to the assembly of microbial communities in the fish gut ‘island’. However, the phylogenetic clustering of local communities and deterministic processes that governed community turnover became less distinct as the fish developed. The observed mechanisms that shaped fish gut microbiota seemed to be mainly shaped by the gut environment and by some other selective changes accompanying the host development process. These findings greatly enhance our understanding of stage‐specific community assembly patterns in the fish gut ecosystem.

Genome-wide analysis of the terpene synthase gene family in physic nut (Jatropha curcas L.) and functional identification of six terpene synthases - Wangdan Xiong; Pingzhi Wu; Yongxia Jia; Xiaoyi Wei; Liangxiong Xu; Yanfang Yang; Deyou Qiu; Yaping Chen; Meiru Li; Huawu Jiang; Guojiang Wu (Tree Genetics & Genomes, 2016)

Cloning and characterization of Bax1 and Bax2 genes of Ctenopharyngodon idellus and evaluation of transcript expression in response to grass carp reovirus infection - Hao Wang; Libo He; Yongyan Pei; Pengfei Chu; Rong Huang; Yongming Li; Lanjie Liao; Zuoyan Zhu; Yaping Wang (Fish Physiology and Biochemistry, 2016)

Flood-ebb asymmetry in current velocity and suspended sediment transport in the Changjiang Estuary - Zhanhai Li; Yaping Wang; Peng Cheng; Guoan Zhang; Jiufa Li (Acta Oceanologica Sinica, 2016)

NO is involved in spermidine-induced drought tolerance in white clover via activation of antioxidant enzymes and genes - Dandan Peng; Xiaojuan Wang; Zhou Li; Yan Zhang; Yan Peng; Yaping Li; Xiaoshuang He; Xinquan Zhang; Xiao Ma; Linkai Huang; Yanhong Yan (Protoplasma, 2016)

Tissue expression analysis, cloning and characterization of the 5′-regulatory region of the bovine FABP3 gene - Anning Li; Lijuan Wu; Xiaoyu Wang; Yaping Xin; Linsen Zan (Molecular Biology Reports, 2016)

Neuroprotective Effect of Osthole on Neuron Synapses in an Alzheimer’s Disease Cell Model via Upregulation of MicroRNA-9 - Shaoheng Li; Yuhui Yan; Yanan Jiao; Zhong Gao; Yang Xia; Liang Kong; Yingjia Yao; Zhenyu Tao; Jie Song; Yaping Yan; Guangxian Zhang; Jingxian Yang (Journal of Molecular Neuroscience, 2016)

Isolation and functional characterization of a cold responsive phosphatidylinositol transfer-associated protein, ZmSEC14p, from maize (Zea may L.) - Xiaoyu Wang; Xiaohui Shan; Chunmei Xue; Ying Wu; Shengzhong Su; Shipeng Li; Hongkui Liu; Yuan Jiang; Yanfei Zhang; Yaping Yuan (Plant Cell Reports, 2016)

Luman recruiting factor is involved in stromal cell proliferation during decidualization in mice - Xiao Li; Pengfei Lin; Fenglei Chen; Nan Wang; Fan Zhao; Aihua Wang; Yaping Jin (Cell and Tissue Research, 2016)

Effects of Land Use Change on Phosphorus Levels in Surface Waters—a Case Study of a Watershed Strongly Influenced by Agriculture - Bin Zhou; Yaping Xu; Rolf D. Vogt; Xueqiang Lu; Xuemei Li; Xiaowen Deng; Ang Yue; Liang Zhu (Water, Air, & Soil Pollution, 2016)

A Brachypodium distachyon MAPKK Gene BdMKK6.2 Negatively Regulates Drought Stress Tolerance in Transgenic Tobacco Plants - Jiutong Sun; Run Zhou; Yaping Li; Wei Hu; Ding Qiu; Xiatian Wang; Qiong Wang; Zhijuan Feng; Lianzhe Wang; Yi Zhou; Guangyuan He; Guangxiao Yang (Journal of Plant Growth Regulation, 2016)

A Fluorescent Switch Sensor for Glutathione Detection Based on Mn-doped CdTe Quantum Dots - Methyl Viologen Nanohybrids - Lurong Yu; Li Li; Yaping Ding; Yaxiang Lu (Journal of Fluorescence, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Kupffer-cell-expressed transmembrane TNF-α is a major contributor to lipopolysaccharide and D-galactosamine-induced liver injury - Peng Yang; Wenjing Zhou; Chenxi Li; Meng Zhang; Yaping Jiang; Rui Jiang; Hongping Ba; Cheng Li; Jing Wang; Bingjiao Yin; Feili Gong; Zhuoya Li (Cell and Tissue Research, 2016)

Experimental models of neuromyelitis optica: current status, challenges and future directions - Minshu Li; Yaping Yan (Neuroscience Bulletin, 2015)

Fingolimod alters inflammatory mediators and vascular permeability in intracerebral hemorrhage - Yu-Jing Li; Guo-Qiang Chang; Yuanchu Liu; Ye Gong; Chunsheng Yang; Kristofer Wood; Fu-Dong Shi; Ying Fu; Yaping Yan (Neuroscience Bulletin, 2015)

Molecular and biochemical characterizations of a new low-temperature active mannanase - Rui Zhang; Junpei Zhou; Yajie Gao; Yaping Guan; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Zunxi Huang (Folia Microbiologica, 2015)

High-level expression and characterization of a thermophilic β-mannanase from Aspergillus niger in Pichia pastoris - Shi Yu; Zhezhe Li; Yaping Wang; Wanping Chen; Lin Fu; Wei Tang; Chen Chen; Yunyun Liu; Xue Zhang; Lixin Ma (Biotechnology Letters, 2015)

Erratum to: Tamlana nanhaiensis sp. nov., isolated from surface seawater collected from the South China Sea - Xiupian Liu; Qiliang Lai; Yaping Du; Guangyu Li; Fengqin Sun; Zongze Shao (Antonie van Leeuwenhoek, 2015)

A Simple Fluorescence Quenching Method for the Determination of Vanillin Using TGA-capped CdTe/ZnS Nanoparticles as Probes - Li Li; Qiaolin Zhang; Yaping Ding; Yaxiang Lu; Xiaoyong Cai; Lurong Yu (Journal of Fluorescence, 2015)

A recombinant canine distemper virus expressing a modified rabies virus glycoprotein induces immune responses in mice - Zhili Li; Jigui Wang; Daoli Yuan; Shuang Wang; Jiazeng Sun; Bao Yi; Qiang Hou; Yaping Mao; Weiquan Liu (Virus Genes, 2015)

Tamlana nanhaiensis sp. nov., isolated from surface seawater collected from the South China Sea - Xiupian Liu; Qiliang Lai; Yaping Du; Guangyu Li; Fengqin Sun; Zongze Shao (Antonie van Leeuwenhoek, 2015)

Pseudooceanicola atlanticus gen. nov. sp. nov., isolated from surface seawater of the Atlantic Ocean and reclassification of Oceanicola batsensis, Oceanicola marinus, Oceanicola nitratireducens, Oceanicola nanhaiensis, Oceanicola antarcticus and Oceanicola flagellatus, as Pseudooceanicola batsensis comb. nov., Pseudooceanicola marinus comb. nov., Pseudooceanicola nitratireducens comb. nov., Pseudooceanicola nanhaiensis comb. nov., Pseudooceanicola antarcticus comb. nov., and Pseudooceanicola flagellatus comb. nov. - Qiliang Lai; Guizhen Li; Xiupian Liu; Yaping Du; Fengqin Sun; Zongze Shao (Antonie van Leeuwenhoek, 2015)

Emcibacter nanhaiensis gen. nov. sp. nov., isolated from sediment of the South China Sea - Xiupian Liu; Guangyu Li; Qiliang Lai; Fengqin Sun; Yaping Du; Zongze Shao (Antonie van Leeuwenhoek, 2015)

Development and characterization of 16 polymorphic microsatellite markers for the highly invasive ascidian, Ciona savignyi - Ping Ni; Yaping Lin; Yiyong Chen; Haitao Li; Yan Zhao; Aibin Zhan (Conservation Genetics Resources, 2015)

The Brachypodium distachyon BdWRKY36 gene confers tolerance to drought stress in transgenic tobacco plants - Jiutong Sun; Wei Hu; Run Zhou; Lianzhe Wang; Xiatian Wang; Qiong Wang; Zhijuan Feng; Yaping Li; Ding Qiu; Guangyuan He; Guangxiao Yang (Plant Cell Reports, 2015)

Alterations of natural killer cells in traumatic brain injury - Xiao-Dong Kong; Sheng Bai; Xin Chen; Hui-Jie Wei; Wei-Na Jin; Min-Shu Li; Yaping Yan; Fu-Dong Shi (Neuroscience Bulletin, 2014)

Efficient Knockout of Transplanted Green Fluorescent Protein Gene in Medaka Using TALENs - Chao Qiu; Bin Cheng; Yunsheng Zhang; Rong Huang; Lanjie Liao; Yongming Li; Daji Luo; Wei Hu; Yaping Wang (Marine Biotechnology, 2014)

Development of 39 novel polymorphic microsatellite markers for the giant mottled eel Anguilla marmorata and cross-amplification in other eel species - Xiaolu Wang; Fang Xu; Li Li; Yaping Zhang; Yandong Ding; Xue Zang; Yihe Jia; Guosong Zhang; Yayuan Wang; Xiaojun Wang; Hongwei Zhang; Shaowu Yin (Conservation Genetics Resources, 2014)

Expression and functional analysis of a glycoside hydrolase family 45 endoglucanase from Rhizopus stolonifer - Bin Tang; Yingying Zhang; Yaping Yang; Zhewei Song; Xianglin Li (World Journal of Microbiology and Biotechnology, 2014)

Directed Self-assembled Nanoparticles of Probucol Improve Oral Delivery: Fabrication, Performance and Correlation - Zhiwen Zhang; Shijun Jiang; Zeying Liu; Baohua Niu; Wangwen Gu; Yaping Li; Jingbin Cui (Pharmaceutical Research, 2014)

Actibacterium atlanticum sp. nov., isolated from surface seawater of the Atlantic Ocean - Guizhen Li; Qiliang Lai; Fengqin Sun; Yaping Du; Xiupian Liu; Guangyu Li; Yunbiao Xie; Zongze Shao (Antonie van Leeuwenhoek, 2014)

Aquimarina atlantica sp. nov., isolated from surface seawater of the Atlantic Ocean - Guizhen Li; Qiliang Lai; Fengqin Sun; Xiupian Liu; Yunbiao Xie; Yaping Du; Guangyu Li; Zongze Shao (Antonie van Leeuwenhoek, 2014)

GRP78 expression and regulation in the mouse uterus during embryo implantation - PengFei Lin; YaPing Jin; XiangLi Lan; YanZhou Yang; Fenglei Chen; Nan Wang; Xiao Li; YuJie Sun; AiHua Wang (Journal of Molecular Histology, 2014)

Erratum to: Maricoccus atlantica gen. nov. sp. nov., isolated from deep sea sediment of the Atlantic Ocean - Guizhen Li; Qiliang Lai; Xiupian Liu; Fengqin Sun; Yaping Du; Guangyu Li; Zongze Shao (Antonie van Leeuwenhoek, 2014)

Transcriptome Profile Analysis of Maize Seedlings in Response to High-salinity, Drought and Cold Stresses by Deep Sequencing - Xiaohui Shan; Yidan Li; Yu Jiang; Zhilei Jiang; Wenyuan Hao; Yaping Yuan (Plant Molecular Biology Reporter, 2013)

Maricoccus atlantica gen. nov. sp. nov., isolated from deep sea sediment of the Atlantic Ocean - Guizhen Li; Qiliang Lai; Xiupian Liu; Fengqin Sun; Yaping Du; Guangyu Li; Zongze Shao (Antonie van Leeuwenhoek, 2013)

Hepatocyte Nuclear Factor 4 Alpha and Farnesoid X Receptor Co-regulates Gene Transcription in Mouse Livers on a Genome-Wide Scale - Ann M. Thomas; Steve N. Hart; Guodong Li; Hong Lu; Yaping Fang; Jianwen Fang; Xiao-bo Zhong; Grace L. Guo (Pharmaceutical Research, 2013)

Mutation screen and RNA analysis disclose the changed splicing of the E-cadherin transcription in gastric cancer - Xiaowei Li; Yafan Gao; Yiyuan Pan; Yan Pan; Lifeng Wang; Nong Xiao; Qiong He; Yimei Fan; Yaping Wang (Familial Cancer, 2013)

Anti-MS4a4B treatment abrogates MS4a4B-mediated protection in T cells and ameliorates experimental autoimmune encephalomyelitis - Yaping Yan; Zichen Li; Guang-Xian Zhang; Mark S. Williams; Gregory B. Carey; Jianke Zhang; Abdolmohamad Rostami; Hui Xu (Apoptosis, 2013)

Effect of household and commercial processing on acetamiprid, azoxystrobin and methidathion residues during crude rapeseed oil production - Yaping Jiang; Takayuki Shibamoto; Yanjie Li; Canping Pan (Food Additives & Contaminants: Part A, 2013)

Comparative proteomic analysis of the H99 inbred maize (Zea mays L.) line in embryogenic and non-embryogenic callus during somatic embryogenesis - Lifang Sun; Ying Wu; Hongda Zou; Shengzhong Su; Shipeng Li; Xiaohui Shan; Jinghui Xi; Yaping Yuan (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Analysis of the DNA methylation of maize (Zea mays L.) in response to cold stress based on methylation-sensitive amplified polymorphisms - Xiaohui Shan; Xiaoyu Wang; Guang Yang; Ying Wu; Shengzhong Su; Shipeng Li; Hongkui Liu; Yaping Yuan (Journal of Plant Biology, 2013)

Sedimentation and morphological changes at Yuantuojiao Point, estuary of the North Branch, Changjiang River - Li Xie; Zhenke Zhang; Yunfeng Zhang; Yaping Wang; Xianjin Huang (Acta Oceanologica Sinica, 2013)

Antigenic analysis of grass carp reovirus using single-chain variable fragment antibody against IgM from Ctenopharyngodon idella - CongLin Chen; XiaoYun Sun; LanJie Liao; ShaoXiang Luo; ZhouQuan Li; XiaoHua Zhang; YaPing Wang; QionLin Guo; Qin Fang; HePing Dai (Science China Life Sciences, 2013)

Enlargement of anode for enhanced simultaneous azo dye decolorization and power output in air-cathode microbial fuel cell - Jian Sun; Youming Li; Yongyou Hu; Bin Hou; Qian Xu; Yaping Zhang; Sizhe Li (Biotechnology Letters, 2012)

The Effects of Ce on the Proliferation, Osteogenic Differentiation and Mineralization Function of MC3T3-E1 Cells In Vitro - Dandan Liu; Jinchao Zhang; Yaping Li; Shuxiang Wang; MengSu Yang (Biological Trace Element Research, 2012)

The complete mitochondrial genome of the butterfly Apatura metis (Lepidoptera: Nymphalidae) - Min Zhang; Xinping Nie; Tianwen Cao; Juping Wang; Tao Li; Xiaonan Zhang; Yaping Guo; Enbo Ma; Yang Zhong (Molecular Biology Reports, 2012)

Differential gene expression during somatic embryogenesis in the maize (Zea mays L.) inbred line H99 - Lifang Sun; Ying Wu; Shengzhong Su; Hongkui Liu; Guang Yang; Shipeng Li; Xiaohui Shan; Yaping Yuan (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Spontaneous uptake of exogenous DNA by goat spermatozoa and selection of donor bucks for sperm-mediated gene transfer - Yongju Zhao; Mingju Yu; Lingbin Wang; Yaofeng Li; Jingsheng Fan; Qian Yang; Yaping Jin (Molecular Biology Reports, 2012)

Determination of Paracetamol Based on its Quenching Effect on the Photoluminescence of CdTe Fluorescence Probes - Li Li; Yaxiang Lu; Yaping Ding; Yu Cheng; Wanchen Xu; Fenfen Zhang (Journal of Fluorescence, 2012)

Distribution and dispersal pattern of clay minerals in surface sediments, eastern Beibu Gulf, South China Sea - Jun Li; Jianhua Gao; Yaping Wang; Yan Li; Fenglong Bai; Laban Cees (Acta Oceanologica Sinica, 2012)

Molecular characterization, expression pattern, polymorphism and association analysis of bovine ADAMTSL3 gene - Yongfeng Liu; Linsen Zan; Shuanping Zhao; Yaping Xin; Yang Jiao; Kui Li (Molecular Biology Reports, 2012)

Association between polymorphisms in the signal transducer and activator of transcription and dilated cardiomyopathy in the Chinese Han population - Ying Peng; Bin Zhou; Yanyun Wang; Yu Chen; Hui Li; Yaping Song; Lin Zhang; Li Rao (Molecular and Cellular Biochemistry, 2012)

Synergistic or Antagonistic Effect of MTE plus TF or Icariin from Epimedium koreanum on the Proliferation and Differentiation of Primary Osteoblasts In Vitro - Jinchao Zhang; Yaping Li; Jing Sun; Cuilian Liu; Dawei Zhang (Biological Trace Element Research, 2011)

Population genetic structure and phylogeographical pattern of rice grasshopper, Oxya hyla intricata, across Southeast Asia - Tao Li; Min Zhang; Yanhua Qu; Zhumei Ren; Jianzhen Zhang; Yaping Guo; K. L. Heong; Bong Villareal; Yang Zhong; Enbo Ma (Genetica, 2011)

Residue Dynamic of Pyrimorph on Tomatoes, Cucumbers and Soil under Greenhouse Trails - Jing Wang; Lianlian Zhao; Xuesheng Li; Yaping Jiang; Nan Li; Zhaohai Qin; Canping Pan (Bulletin of Environmental Contamination and Toxicology, 2011)

Effects of exogenous glutathione on arsenic burden and NO metabolism in brain of mice exposed to arsenite through drinking water - Yan Wang; Fenghong Zhao; Yaping Jin; Yuan Zhong; Xiaoyun Yu; Gexin Li; Xiuqiang Lv; Guifan Sun (Archives of Toxicology, 2011)

Poly(ε-caprolactone)-Block-poly(ethyl Ethylene Phosphate) Micelles for Brain-Targeting Drug Delivery: In Vitro and In Vivo Valuation - Pengcheng Zhang; Luojuan Hu; Yucai Wang; Jun Wang; Linyin Feng; Yaping Li (Pharmaceutical Research, 2010)

Molecular characterization, polymorphism of bovine ZBTB38 gene and association with body measurement traits in native Chinese cattle breeds - Yongfeng Liu; Linsen Zan; Shuanping Zhao; Yaping Xin; Linqiang Li; Wentao Cui; Zhonglin Tang; Kui Li (Molecular Biology Reports, 2010)

Ratiometric and Selective Fluorescent Sensor for F− Based on Intramolecular Charge Transfer (ICT) - Yaping Li; Hai Lin; Huakuan Lin (Journal of Fluorescence, 2010)

Application of Functionalized ZnSe Nanoparticles to Determinate Heavy Metal Ions - Fenfen Zhang; Li Li; Yaping Ding; Yaping Wang (Journal of Fluorescence, 2010)

Delineating suspended sediment concentration patterns in surface waters of the Changjiang Estuary by remote sensing analysis - Jing Li; Shu Gao; Yaping Wang (Acta Oceanologica Sinica, 2010)

Znrg, a novel gene expressed mainly in the developing notochord of zebrafish - Yaping Zhou; Yan Xu; Jianzhen Li; Yao Liu; Zhe Zhang; Fengjiao Deng (Molecular Biology Reports, 2010)

Dissipation and Residues Detection of Dioctyldiethylenetriamine Cetate in Rice Plant and Environment by QuEChERS Method and Liquid Chromatography/Electrospray Tandem Mass Spectrometry - Xuesheng Li; Yaping Jiang; Weili Shan; Canping Pan (Bulletin of Environmental Contamination and Toxicology, 2010)

Invading cord grass vegetation changes analyzed from Landsat-TM imageries: a case study from the Wanggang area, Jiangsu coast, eastern China - Jing Li; Shu Gao; Yaping Wang (Acta Oceanologica Sinica, 2010)

The role of MC1R gene in buffalo coat color - YongWang Miao; GuiSheng Wu; Lei Wang; DaLin Li; ShouKun Tang; JianPing Liang; HuaMing Mao; HuaiRong Luo; YaPing Zhang (Science China Life Sciences, 2010)

The application of geostatistics in grain size trend analysis: A case study of eastern Beibu Gulf - Fei Ma; Yaping Wang; Yan Li; Changjiang Ye; Zhiwei Xu; Fan Zhang (Journal of Geographical Sciences, 2010)

Design of Two Pyrazole-Based Sensors with Similar Configuration and Different Fluorescent Response to Anions - Yaping Li; Jie Shao; Xudong Yu; Xiufang Xu; Hai Lin; Zunsheng Cai; Huakuan Lin (Journal of Fluorescence, 2010)

Identification and characterization of HTD2: a novel gene negatively regulating tiller bud outgrowth in rice - Wenzhen Liu; Chao Wu; Yaping Fu; Guocheng Hu; Huamin Si; Li Zhu; Weijiang Luan; Zhengquan He; Zongxiu Sun (Planta, 2009)

The Polymorphism of DNA Repair Gene ERCC2/XPD Arg156Arg and Susceptibility to Breast Cancer in a Chinese Population - Jiaoyang Yin; Duohong Liang; Ulla Vogel; Yaping Chang; Zhengrong Liu; Li Yue; Xiaoling Sun; Rong Qi; Tiehua Song (Biochemical Genetics, 2009)

A quick isolation method for mutants with high lipid yield in oleaginous yeast - Jufang Wang; Renmin Li; Dong Lu; Shuang Ma; Yaping Yan; Wenjian Li (World Journal of Microbiology and Biotechnology, 2009)

Synthesis of Functionalized ZnSe Nanoparticles and Their Applications in the Determination of Bovine Serum Albumin - Li Li; Fenfen Zhang; Yaping Ding; Yaping Wang; Lulu Zhang (Journal of Fluorescence, 2009)

Optimization of fermentation conditions for production of xylanase by a newly isolated strain, Penicillium thiersii ZH-19 - Fengjie Cui; Yin Li; Zhiqiang Liu; Hui Zhao; Lifeng Ping; Liying Ping; Yinan Yang; Yaping Xue; Lijiao Yan (World Journal of Microbiology and Biotechnology, 2009)

Urinary Arsenic Speciation and its Correlation with 8-OHdG in Chinese Residents Exposed to Arsenic Through Coal Burning - Xin Li; Jingbo Pi; Bing Li; Yuanyuan Xu; Yaping Jin; Guifan Sun (Bulletin of Environmental Contamination and Toxicology, 2008)

Effects of in utero meso-2,3-dimercaptosuccinic acid with calcium and ascorbic acid on lead-induced fetal development - Fei Yu; Yingjun Liao; Yaping Jin; Yue Zhao; Yahao Ren; Chunwei Lu; Gexin Li; Yanxi Li; Jun Yang (Archives of Toxicology, 2008)

Therapeutic potentials of combined use of DMSA with calcium and ascorbic acid in the treatment of mild to moderately lead intoxicated mice - Yingjun Liao; Jun Zhang; Yaping Jin; Chunwei Lu; Gexin Li; Fei Yu; Xuping Zhi; Li An; Jun Yang (BioMetals, 2008)

Spatial distributions of organic carbon and nitrogen and their isotopic compositions in sediments of the Changjiang Estuary and its adjacent sea area - Jianhua Gao; Yaping Wang; Shaoming Pan; Rui Zhang; Jun Li; Fenglong Bai (Journal of Geographical Sciences, 2008)

Selection of micronutrients used along with DMSA in the treatment of moderately lead intoxicated mice - Yingjun Liao; Fei Yu; Yaping Jin; Chunwei Lu; Gexin Li; Xuping Zhi; Li An; Jun Yang (Archives of Toxicology, 2008)

Identification and fine mapping of a thermo-sensitive chlorophyll deficient mutant in rice (Oryza sativa L.) - Wenzhen Liu; Yaping Fu; Guocheng Hu; Huamin Si; Li Zhu; Chao Wu; Zongxiu Sun (Planta, 2007)

Genetic Variation and Population Structure of Oriental Migratory Locust, Locusta migratoria manilensis, in China by Allozyme, SSRP-PCR, and AFLP Markers - Xianyun Zheng; Yang Zhong; Yihao Duan; Chunxuan Li; Li Dang; Yaping Guo; Enbo Ma (Biochemical Genetics, 2006)

Mutational analysis of the mitochondrial 12S rRNA gene in Chinese pediatric subjects with aminoglycoside-induced and non-syndromic hearing loss - Zhiyuan Li; Ronghua Li; Jianfu Chen; Zhisu Liao; Yi Zhu; Yaping Qian; Sudao Xiong; Selena Heman-Ackah; Jianbo Wu; Daniel I. Choo; Min-Xin Guan (Human Genetics, 2005)

Numerical Simulation of Drag Partition over Rough Surfaces - An Li; Yaping Shao (Boundary-Layer Meteorology, 2003)

Multiple origins of Tibetan Y chromosomes - Yaping Qian; Binzhi Qian; Bing Su; Jiankun Yu; Yuehai Ke; Zhengtao Chu; Lei Shi; Daru Lu; Jiayou Chu; Li Jin (Human Genetics, 2000)

Numerical Modelling of Saltation in the Atmospheric Surface Layer - Yaping Shao; An Li (Boundary-Layer Meteorology, 1999)

An observational study of the 30–50 day atmospheric oscillations part II: Temporal evolution and hemispheric interaction across the equator - Li Chongyin; Zhou Yaping (Advances in Atmospheric Sciences, 1991)